JP2000516983A - Fluoropolymer-epoxy resin semi-interpenetrating network composition - Google Patents

Fluoropolymer-epoxy resin semi-interpenetrating network composition

Info

Publication number
JP2000516983A
JP2000516983A JP10511654A JP51165498A JP2000516983A JP 2000516983 A JP2000516983 A JP 2000516983A JP 10511654 A JP10511654 A JP 10511654A JP 51165498 A JP51165498 A JP 51165498A JP 2000516983 A JP2000516983 A JP 2000516983A
Authority
JP
Japan
Prior art keywords
fluoropolymer
epoxy resin
composition
poly
semi
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
JP10511654A
Other languages
Japanese (ja)
Other versions
JP2000516983A5 (en
Inventor
エー. ペレツ,マリオ
ディー. コッジオ,ウィリアム
エス. パーカー,ダグラス
シー. パラゾット,マイケル
Original Assignee
ミネソタ マイニング アンド マニュファクチャリング カンパニー
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by ミネソタ マイニング アンド マニュファクチャリング カンパニー filed Critical ミネソタ マイニング アンド マニュファクチャリング カンパニー
Publication of JP2000516983A publication Critical patent/JP2000516983A/en
Publication of JP2000516983A5 publication Critical patent/JP2000516983A5/ja
Pending legal-status Critical Current

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
    • C08L63/00—Compositions of epoxy resins; Compositions of derivatives of epoxy resins
    • C—CHEMISTRY; METALLURGY
    • C09—DYES; PAINTS; POLISHES; NATURAL RESINS; ADHESIVES; COMPOSITIONS NOT OTHERWISE PROVIDED FOR; APPLICATIONS OF MATERIALS NOT OTHERWISE PROVIDED FOR
    • C09D—COATING COMPOSITIONS, e.g. PAINTS, VARNISHES OR LACQUERS; FILLING PASTES; CHEMICAL PAINT OR INK REMOVERS; INKS; CORRECTING FLUIDS; WOODSTAINS; PASTES OR SOLIDS FOR COLOURING OR PRINTING; USE OF MATERIALS THEREFOR
    • C09D163/00—Coating compositions based on epoxy resins; Coating compositions based on derivatives of epoxy resins
    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
    • C08L27/00—Compositions of homopolymers or copolymers of compounds having one or more unsaturated aliphatic radicals, each having only one carbon-to-carbon double bond, and at least one being terminated by a halogen; Compositions of derivatives of such polymers
    • C08L27/02—Compositions of homopolymers or copolymers of compounds having one or more unsaturated aliphatic radicals, each having only one carbon-to-carbon double bond, and at least one being terminated by a halogen; Compositions of derivatives of such polymers not modified by chemical after-treatment
    • C08L27/12—Compositions of homopolymers or copolymers of compounds having one or more unsaturated aliphatic radicals, each having only one carbon-to-carbon double bond, and at least one being terminated by a halogen; Compositions of derivatives of such polymers not modified by chemical after-treatment containing fluorine atoms
    • C—CHEMISTRY; METALLURGY
    • C09—DYES; PAINTS; POLISHES; NATURAL RESINS; ADHESIVES; COMPOSITIONS NOT OTHERWISE PROVIDED FOR; APPLICATIONS OF MATERIALS NOT OTHERWISE PROVIDED FOR
    • C09D—COATING COMPOSITIONS, e.g. PAINTS, VARNISHES OR LACQUERS; FILLING PASTES; CHEMICAL PAINT OR INK REMOVERS; INKS; CORRECTING FLUIDS; WOODSTAINS; PASTES OR SOLIDS FOR COLOURING OR PRINTING; USE OF MATERIALS THEREFOR
    • C09D127/00—Coating compositions based on homopolymers or copolymers of compounds having one or more unsaturated aliphatic radicals, each having only one carbon-to-carbon double bond, and at least one being terminated by a halogen; Coating compositions based on derivatives of such polymers
    • C09D127/02—Coating compositions based on homopolymers or copolymers of compounds having one or more unsaturated aliphatic radicals, each having only one carbon-to-carbon double bond, and at least one being terminated by a halogen; Coating compositions based on derivatives of such polymers not modified by chemical after-treatment
    • C09D127/12—Coating compositions based on homopolymers or copolymers of compounds having one or more unsaturated aliphatic radicals, each having only one carbon-to-carbon double bond, and at least one being terminated by a halogen; Coating compositions based on derivatives of such polymers not modified by chemical after-treatment containing fluorine atoms
    • C—CHEMISTRY; METALLURGY
    • C08—ORGANIC MACROMOLECULAR COMPOUNDS; THEIR PREPARATION OR CHEMICAL WORKING-UP; COMPOSITIONS BASED THEREON
    • C08L—COMPOSITIONS OF MACROMOLECULAR COMPOUNDS
    • C08L2205/00—Polymer mixtures characterised by other features
    • C08L2205/04—Polymer mixtures characterised by other features containing interpenetrating networks

Landscapes

  • Chemical & Material Sciences (AREA)
  • Organic Chemistry (AREA)
  • Life Sciences & Earth Sciences (AREA)
  • Medicinal Chemistry (AREA)
  • Polymers & Plastics (AREA)
  • Chemical Kinetics & Catalysis (AREA)
  • Health & Medical Sciences (AREA)
  • Engineering & Computer Science (AREA)
  • Materials Engineering (AREA)
  • Wood Science & Technology (AREA)
  • Epoxy Resins (AREA)
  • Compositions Of Macromolecular Compounds (AREA)
  • Paints Or Removers (AREA)
  • Adhesives Or Adhesive Processes (AREA)

Abstract

(57)【要約】 硬化可能なエポキシ樹脂と、該硬化可能なエポキシ樹脂のための有効量の硬化剤と、十分に予備重合された未架橋フルオロポリマーと、必要に応じてポリオレフィンまたはポリアミドとを含む硬化可能な組成物。20重量パーセントまでのフルオロポリマーを脱フッ化水素化して、基材との接着性が増強した半−IPNを提供することができる。該フルオロポリマー−エポキシ半IPNは、保護被覆、接着テープを含む接着剤としておよび多層集成物において有用である。   (57) [Summary] Curable composition comprising a curable epoxy resin, an effective amount of a curing agent for the curable epoxy resin, a fully prepolymerized uncrosslinked fluoropolymer, and optionally a polyolefin or polyamide. . Up to 20 weight percent of the fluoropolymer can be dehydrofluorinated to provide a semi-IPN with enhanced adhesion to the substrate. The fluoropolymer-epoxy semi-IPN is useful as protective coatings, adhesives, including adhesive tapes, and in multilayer assemblies.

Description

【発明の詳細な説明】 フルオロポリマー−エポキシ樹脂半相互貫入網目構造組成物 技術分野 本発明は、十分に予備重合された熱可塑性フルオロポリマーの存在下において 熱硬化性樹脂(すなわち、エポキシ樹脂)を重合することによって調製された、 熱可塑性樹脂と熱硬化性樹脂との半−相互貫入ポリマー網目構造(半−IPN) に関する。本発明はまた、固形物100%の処理およびエポキシ樹脂の潜在硬化 または後硬化を特徴とする、半−IPNを製造する方法並びにこの方法によって 製造される半−IPNを提供する。 背景技術 硬化物を強靱にするために(すなわち、延性を増すために)硬化可能な熱硬化 性樹脂に少量のエラストマー材料または熱可塑性材料を配合することは産業上普 通に実施されることである。エラストマーまたは熱可塑性硬化剤には、天然ゴム 、ポリオレフィンおよびポリ(スチレン−コ−ブタジエン)が含まれる。このよ うな場合には、熱可塑性組成物が熱硬化性樹脂中で分散相になって連続相となる ように、硬化剤を約1:20〜約1:4の比で配合する。例えば、米国特許第4 ,861,647号および同第5,008,135号を参照のこと。 フルオロポリマーと熱硬化性樹脂との溶媒をベースとした配合物は腐食保護の ための金属基材の被覆として有用であるとして米国特許第3,784,506号 および4,179,542号に記載されている。これらの被覆は、固形樹脂と分 散媒とをボールミルまたは 高せん断混合し、次に一般にはスプレーコーティングによって金属基材にこの分 散物を適用し、その後250℃までの温度で加熱することによって形成される。 固形物100%の半−IPNの被覆については記載されていない。 エポキシドの光開始カチオン重合は周知である。有機アリールスルホニウムお よびアリールヨードニウム塩は好適な光開始剤、すなわち、光線の照射により、 例えばエポキシド重合を開始するプロトンを放出する化合物として認められる。 また、ある種の金属−アレン有機金属錯塩はカチオン重合のための光開始剤とし て記載されている。これらの場合には、カチオン重合性成分はモノマーである。 発明の開示 簡単には、本発明は硬化可能な組成物であって: a)硬化可能なエポキシ樹脂と、 b)該硬化可能なエポキシ樹脂のための、有効量の硬化剤と、 c)十分に予備重合された未架橋フルオロポリマーと、 d)必要に応じて、ポリオレフィンまたはポリアミドと を含有し、溶媒を含まない組成物を提供する。 好ましくは、エポキシ成分は、総組成物に対して0から75重量パーセントま で、さらに好ましくは0から70重量パーセントまで、よりさらに好ましくは0 から40重量パーセントまで、最も好ましくは0.5から15重量パーセントま での範囲で存在し、フルオロポリマーは、総組成物に対して25から100重量 パーセント末満、さらに好ましくは30から100重量パーセント未満、よりさ らに好ましくは60から100重量パーセント未満、最も好ましくは85から9 5.5重量パーセントの範囲で存在する。組成物は好ましくは、硬化後のエポキ シ骨格にフッ素を物理的に組込む硬化剤を含 まない。 別の態様において、本発明は熱硬化および/または光化学硬化エポキシ樹脂と 十分に予備重合されたフルオロポリマーとを含有する半−相互貫入ポリマー網目 構造について記載する。 別の態様において、本発明は、半−IPNを製造する方法であって、(a)溶 媒の非存在下において、光化学−または熱−硬化可能なエポキシ樹脂樹脂および このエポキシ樹脂のための、光硬化剤または高温に安定な熱硬化剤のうちの少な くとも一方の存在下において、好ましくは両者とも未架橋であるポリオレフィン およびポリアミドの一方または両方を必要に応じて組み合わせて、十分に予備重 合されたフルオロポリマーをよく混ぜて混合するステップと、(b)必要に応じ て、溶媒を含まない混合物を基材に適用するステップと、(c)混合後の任意の 時間経過時に、混合物に十分な熱および/または光エネルギーを供給することに よって、硬化剤または光触媒を活性化するステップとを含む方法について記載す る。 さらに別の態様のおいて、必要に応じてポリオレフィンまたはポリアミドの存 在下において、エポキシモノマーと合わせる前にフルオロポリマーを脱フッ化水 素化することにより、基材との接着性が増した半−IPNを提供する。 当技術分野においてこれまで記載されておらず、本発明によって提供されるも のは、必要に応じてポリオレフィンまたはポリアミドの存在下において、硬化可 能な熱硬化性樹脂、すなわちエポキシ樹脂とそのための硬化剤と、必要に応じて 十分に予備重合されたフルオロエラストマーとを含有し、硬化可能なエポキシ樹 脂が、硬化剤としてAr3SSbF6(式中、「Ar」は、例えばフェニルなどの 芳香族種をいう)またはフルオレンアミンなどの好適なオニウム塩光開始剤の存 在下において、その場において、有用な形態に成形、 被覆または製造されるまで、硬化条件、すなわち光線、好ましくはによる照射ま たは約170℃より高い温度に好ましくは暴露されない、溶媒を含まない組成物 である。他の硬化剤はさらに高い温度での処理を可能にする。 フルオロポリマー−エポキシ半−IPNは、保護被覆、接着剤としておよび多 層集成物において有用である。さらに特には、本発明の半−IPNは、金属、プ ラスチックもしくはセラミックのための構造接着剤として;自己支持型ホットメ ルト接着剤として;または保護被覆として有用である。好ましい実施態様におい て、フルオロポリマー−エポキシ半−IPNを可撓性基材に被覆して接着テープ を製造することができる。さらに好ましい実施態様において、フルオロポリマー −エポキシ半−IPNを、ガソリンなどの炭化水素燃料の貯蔵または輸送のため に使用され、好ましくはポリオレフィンを含有する、さらに好ましくはポリプロ ピレンを含有するポリマータンクまたは容器に被覆することができ、本発明の半 −IPNは、ポリマー容器と結果として生じるフルオロポリマー(例えば、ポリ (テトラフルオロエチレン(PTFE))保護被覆との間の結合剤として作用する 中間の(すなわち、「結合」)被覆であってもよい。本発明の半−IPNは、腐食 性化学物質の輸送および貯蔵に使用される金属タンクまたは容器の内部被覆とし て直接的な用途も見出される。 この用途において: 「エポキシ樹脂」は硬化可能な材料を意味し、モノ−およびポリエポキシドを 含む; 「骨格」はポリマー主鎖を意味し、側基または末端基を含まない; 「カチオン有機金属塩」は塩、金属原子に結合した有機基の少なくとも1つの 炭素原子を含有するカチオン部分を意味し(「基礎無 機化学(Basic Inorganic Chemistry)」、コットン(F. A.cotton)、ウィルキンソン(G.Wilkinson)、ウィレイ(W iley)社、ニューヨーク、1976年、p497);好ましくは、金属原子 は遷移金属原子である; 「基」は置換を可能にする化学種または望ましい生成物を妨害しない従来の置 換基によって置換されてもよい化学種を意味し、例えば置換基はアルコキシ、フ エニル、ハロ(F、Cl、Br、I)、シアノ、ニトロ等であってもよい。 「半−相互貫入ポリマー網目構造(半−IPN)」は少なくとも1つのポリマー が架橋され、少なくとも1つのポリマーが未架橋である2つ以上のポリマーのポ リマー網目構造を意味する、 「フルオロエラストマー」は、仲張下で仲び、高い引張り強度を有し、速やか に縮み、元の寸法に完全に回復し、限界まで変形されるとき、変形されないよう な可塑性も示すことができるという点において、天然または合成ゴムの特性を有 するフッ素化ポリマーを意味する; 「フルオロポリマー」または「フルオロカーボンポリマー」は、少なくとも1 種のモノマーから製造され、炭素原子に直接結合する水素原子の少なくとも半分 がフッ素原子によって置換されているポリマーを意味する; 「脱フッ化水素化」はポリマーのフルオロカーボン単位からHFを離脱し、ポ リマー中に不飽和単位を生成することを意味する;および、 「硬化剤」、「硬化剤」、「触媒」および「開始剤」は、重合反応に影響を与える ために使用されるいかなる活性または反応性種を意味するために使用され、交換 可能である。 本発明の半−IPNは、フルオロポリマー成分が電気的特性、化 学抵抗および低い使用温度に寄与することができるという点、およびエポキシモ ノマー成分が安定性、組成物の可撓性および組成物の後硬化性に寄与することが できるという点において、有利な特性を有する。 好ましい実施態様の詳細な説明 本発明は硬化可能な組成物であって: a)硬化可能なエポキシ樹脂と、 b)硬化可能なエポキシ樹脂のための有効量の硬化剤と、 c)十分に予備重合された未架橋フルオロポリマーおよび必要に応じてポリオレ フィンまたはポリアミドと を含有する組成物を提供する。 好ましくは、成分の配合は、触媒の熱活性化温度未満の温度、すなわち170 ℃以上、好ましくは170〜400℃の範囲、さらに好ましくは200〜400 ℃の範囲の温度で生じる。 有用なフルオロポリマーは当技術上周知の方法によって製造することができ、 例えばミネソタ州セントポールのディネオン エルエルシー(Dyneon L LC)製の商品名登録商標THV200、THV230、THV500、THV 530、登録商標Fluorel(HFP/VDF)、登録商標Fluorel− II(TFE/PP/VDF)および登録商標Kel−F800、フルオロエラ ストマー;エルフ アトケム ノース アメリカ社(Elf Atochem N orth America Inc.)(ぺンシルバニア州フィラデルフィア)製の 商品名登録商標Kynar740、2800、9301;クレハケミカル社(K ureha Chemical Co.)製の商品名登録商標KFポリマー;ダイ キンアメリカ社(Daikin America,Inc.)(ニューヨーク州 ニューヨーク)製の商品名登録商標NeofluronVDF;セントラルガラ ス(Central Glass)(日本、東京)製の商品名登録商標Cefra l SoftG−150およびアサヒガラス株式会社(Asahi Glass Co.,Ltd.)(日本、東京)製の商品名登録商標AFLAS200を購入し てもよい。 さらに好ましい実施態様において、十分に予備重合されたフルオロポリマーは テトラフルオロエチレンと、ヘキサフルオロプロピレンとフッ化ビニリデンとの ターポリマー(以降、THVと命名、ミネソタ州セントポールのディネオン エ ルエルシー(Dyneon LLC)製)である。最も好ましくは、THV20 0(42モルパーセントTFE、20モルパーセントHFP、30モルパーセン トVDF)を使用する。ターポリマー骨格は以下のモノマーから生ずる単位を含 有する。 THVおよび上記の他のもに加え、本発明に有用となり得るフルオロポリマー には、一般にテトラフルオロエチレン、クロロトリフルオロエチレン、ヘキサフ ルオロプロピレン、フッ化ビニリデン、パーフルオロプロピルビニルエーテルな どのパーフルオロアルキルビニルエーテルおよびトリフルオロエチレンを含む群 から製造されるホモポリマーおよびコポリマーが含まれる。特殊なポリマーには 、ポリ(エチレン−コ−クロロトリフルオロエチレン)(ECTFE)、ポリ(テ トラフルオロエチレン)(PTFE)、ポリ(テトラフルオロエチレン−コ−ヘキ サフルオロプロピレン)(FEP)、ポリ(エチレン−コ−テトラフルオロエチレ ン)(ETFE)、ポリ(エチレン−コ−テトラフルオロエチレン−コ−ヘキサフ ルオロプロピレン)(EFEP)、ポリ(フッ化ビニリデン)(PVDF)および ポリ(クロロトリフルオロエチレン)(PCTFE)が含まれるが、これらに限 定されない。もちろん、本発明に有用となり得る多数の他のフルオロポリマーが 当技術分野上周知である。 別の態様において、エポキシモノマーおよび必要に応じてポリオレフィンまた はポリアミドと合わせる前にフルオロポリマーを脱フッ化水素化することにより 、基材との接着性が増した半−IPNが提供される。本発明の半−IPNに組み 入れるフルオロポリマーの 脱フッ化水素化は、基材に対する望ましい接着特性を提供することができる。フ ルオロポリマー中に存在する脱フッ化水素のモルパーセントは0.01〜20の 範囲、好ましくは0.01〜5.0、さらに好ましくは0.02〜2.0モルパ ーセント、さらに好ましくは0.2〜1.15モルパーセントの範囲であっても よい。 フルオロポリマーは、フルオロポリマーの十分な炭素−炭素不飽和を提供して フルオロポリマーと基材との強い接着強度を形成するいかなる方法によって脱フ ッ化水素化されてもよい。好ましくは、脱フッ化水素化過程はフルオロポリマー にグラフト置換基をあまり導入しない。「かなりの量」は、例えば脱フッ化水素 化フルオロポリマーを含有する共重合モノマーの数に対して、約2モルパーセン トより多い量を意味する。望ましくは、脱フッ化水素化フルオロポリマーを含有 する共重合ポリマー単位の総数に対して、約1モルパーセントより少ない、例え ば約0.5、好ましくは0.2または最も好ましくは0.1モルパーセントより 少ない接着性促進基が脱フッ化水素中にフッ素化ポリマーに導入される。脱フッ 化水素化バルクフルオロポリマーの場合には、多くない量のグラフト置換基のフ ルオロポリマーへの導入は好ましくはフルオロポリマーの物理特性または機械特 性を特定可能なほどに変化させない。 多数の好適な脱フッ化水素化方法はフルオロポリマー技術分野において周知で ある。例えば、バルクフルオロポリマーの脱フッ化水素化は、フルオロポリマー が有機溶媒の溶液に溶解される、溶媒をベースとした方法によって実施されても よい。必要に応じて相転移触媒の存在下において塩基性試薬を溶液に添加して脱 フッ化水素化を生じる。一般的な溶媒にはテトラヒドロフラン、メチルイソブチ ルケトン、メチルエチルケトン、アセトン、n,n−ジメチルホルムアミド、ジ メチルアセトアミド等が含まれる。例えば、米国特許 第3,507,844号、同第4,742,126号および同第4,758,6 18号を参照のこと。または、脱フッ化水素化は、フルオロポリマーを有機溶媒 に溶解し、この溶媒相をアルカリ金属の水酸化物と相転移触媒とを含有する水相 と混合する、2相溶媒法で実施してもよい。有用な触媒はフルオロポリマー技術 分野において周知であり、例えば臭化テトラブチルアンモニウム(TBAB)、テ トラアルキルホスホニウムハライド、アルキルアリールホスホニウムハライド、 アルキルアンモニウムハライドおよびアルキルホスホニウムハライドが含まれる 。米国特許第4,742,126号を参照のこと。さらに別の方法によると、「 反応性押出法」として当技術分野において呼ばれる乾燥バルク脱フッ化水素化法 によってフルオロポリマーを脱フッ化水素化してもよい。これらの方法によって 、例えば押しだし器またはボールミキサーを使用して乾燥塩基性過程によって脱 フッ化水素化を実施する。 水性フルオロポリマー乳化液内でのフルオロポリマーの脱フッ化水素化も比較 的マイルドな条件下において、実質的に有機溶媒を含まない塩基性水性媒体中で 、好ましくは有機溶媒を含有しない100パーセント水性媒体中において、必要 に応じて好適な乳化作用を有する界面活性剤の存在下において実施され得る。こ の水性脱フッ化水素化方法によって、塩基性化台物を、式(I):(式中、XおよびX’は各々独立して、水素または電子吸引基のどちらかである )による構造断片を有するフルオロポリマーを含有するフルオロポリマー乳化物 に添加することができる。フルオロポリマー乳化物に塩基性化合物を添加する結 果、フルオロポリマーを脱フッ化水素化するのに十分なほど水素原子は酸性であ る。 好適な塩基性化合物の例には、エチルアミン、水酸化カリウム(KOH)、水酸 化アンモニウム(NH4OH)、水酸化ナトリウム(NaOH)、水酸化リチウム( LiOH)などの水酸化物;炭酸カリウム(K2CO3)、炭酸ナトリウム(Na2 CO3)などの炭酸塩等が含まれる。 乳化物の安定性を妨害しない量、従ってフルオロポリマーの凝集を生じない量 の塩基性化合物を乳化物に添加する。本明細書において使用される「凝集」とい う用語は乳化物からフルオロポリマーが沈殿する状態をいう。次いで、塩基性化 合物をフルオロポリマーの−CFX−CHX’反応部位と反応させるのに十分な 反応条件に乳化物を置き、それによってフルオロポリマーを水素とフッ素原子を 離脱してフルオロポリマー内に不飽和−CX=CX’−配列を生成することがで きる。水性脱フッ化水素化反応条件(すなわち、反応時間および温度)は、脱フ ッ化水素反応を生じさせ、特定のフルオロポリマーおよび選択した塩基性化合物 並びに得られる脱フッ化水素化フルオロポリマーの望ましい不飽和度に依存して もよいいかなる反応時間およびいかなる反応温度であってもよい。この水性脱フ ッ化水素化法では、反応温度は比較的マイルドで、例えば約40〜100℃の範 囲であってもよい。反応時間はいかなる有用な反応時間であってもよいが、好ま しくは約6〜100時間であってもよい。 フルオロポリマー乳化物内の乳化作用を有する界面活性剤はフルオロポリマー 乳化物の技術分野において周知な種々の乳化界面活性 剤の1つであってもよい。これらには、例えば脂肪酸石鹸などのアニオン界面活 性剤(ステアリン酸、ラウリン酸、パルミチン酸ナトリウムまたはカリウム)、硫 酸塩およびスルホン酸塩(ラウリル硫酸ナトリウムおよびドデシルベンゼンスル ホン酸ナトリウム)、ポリ(エチレンオキサイド)、ポリ(ビニルアルコール)お よびヒドロキシエチルセルロースおよびパーフッ素化カルボン酸を含むフッ素化 界面活性剤などの非イオン界面活性剤が含まれる。これらおよび他の乳化界面活 性剤は単独または2種以上の乳化界面活性剤と併用して使用されてもよく、いか なる有効な量、すなわち乳化物を生じる量で存在してもよい(例えば、ジョージ オーディアン(George Odian)、Principles of Po lymerization、3332−3(第2版、1981)を参照のこと) 上記の脱フッ化水素化法はバルクフルオロポリマー(例えば、フルオロポリマ ー顆粒)またはフルオロポリマー乳化物の脱フッ化水素化に関する。これらのバ ルクおよび乳化物型脱フッ化水素化過程において、フルオロポリマーの脱フッ化 水素化は、好ましくは脱フッ化水素化フルオロポリマーを製造するために使用し た共重合モノマー単位数に対して、約0.01モルパーセント〜20モルパーセ ントの範囲であってもよく、約0.02モルパーセント〜約2.0モルパーセン トの範囲が特に好ましい。 脱フッ化水素化ポリマーを使用した2つの実施態様には以下が含まれる: 1.脱フッ化水素化ポリマーの存在下においてエポキシモノマーの硬化がエポ キシとフルオロポリマー鎖との間にいくつかの化学結合を有する半−IPNを提 供する。 2.脱フッ化水素化ポリマーと官能性(すなわち、酸性化、例え ばマレイン酸化)ポリオレフィンとの配合物の存在下でのエポキシの硬化はエポ キシとフルオロポリマー鎖との間およびエポキシとポリオレフィン鎖との間にい くつかの化学結合を有する半−IPNを提供する。 本発明に有用なエポキシ樹脂は好ましくは、1,2−、1,3−および1,4 −エポキシドとして周知であってもよい、1,2−、1,3−および1,4−環 状エーテルを1つ以上含有する。このような化合物飽和または不飽和、脂肪族、 脂肪族環状、芳香族もしくは複素環であってもよく、またはそれらの組み合わせ を含んでもよい。1つ以上のエポキシ基(すなわち、ポリエポキシド)を含有す る化合物が好ましい。本発明に有用なモノエポキシモノマーには、3−ヒドロキ シ−1,2−ポリエチレンオキサイド、オキサシクロブタン、シクロヘキサンオ キサイド、インデンオキサイド、スチレンオキサイド、ブチルグリシジルエーテ ル、フェニルグリシジルエーテル、クレジルグリシジルエーテル、n−ブチルフ エノールグリシジルエーテル、ビニルシクロヘキサンモノオキサイド、オクチレ ンオキサイド、α−ピネンオキサイド、リモネンオキサイドおよび3−ペンタデ シルフェニルグリシジルエーテルが含まれる。 本発明に使用することができる芳香族ポリエポキシド(すなわち、少なくとも 1つの芳香族環構造を含有する化合物、例えばベンゼン環および2つ以上のエポ キシ基)にはビスフェノールA型樹脂およびそれらの誘導体、エポキシクレゾー ル−ノボラック樹脂、ビスフェノール−F樹脂およびそれらの誘導体ならびにエ ポキシフェノール−ノボラック樹脂などの多価フェノールのポリグリシジルエー テル;および芳香族カルボン酸のグリシジルエステル、例えばフタル酸ジグリシ ジルエステル、イソフタル酸ジグリシジルエステル、無水トリメリト酸トリグリ シジルエステルおよびピロメリト酸テトラ グリシジルエステルおよびそれらの混合物が含まれる。好ましい芳香族ポリエポ キシドは、テキサス州ヒューストンのシェルケミカルズ社(Shell Che micals,Inc.)製のEPON828およびEPON1001Fを含む 、ビスフェノール−Aのジグリシジルエーテルの登録商標EPONシリーズなど の多価フェノールのポリグリシジルエーテルである。 本発明に有用な代表的な脂肪族環状ポリエポキシド(すなわち、脂環式化合物 としても周知である、1つ以上の飽和炭素環および2つ以上のエポキシ基環状化 合物を含有する環状化合物)には、ビニルシクロヘキサンジオキサイド(ERL −4206)、3,4−エポキシシクロヘキシルメチル−3,4−エポキシシク ロヘキサンカルボキシレート(ERL−4221)、3,4−エポキシ−6−メチ ルシクロヘキシルメチル−3,4−エポキシ−6−メチルシクロヘキサンカルボ キシレート(ERL−4201)、ビス(3,4−エポキシ−6−メチルシクロヘ キシルメチル)アジペート(ERL−4289)、ジペンテンジオキサイド(ER L−4269)並びに2−(3,4−エポキシシクロヘキシル−5,1”−スピ ロ−3”,4”−エポキシシクロヘキサン−1,3−ジオキサン、4−(1,2 −エポキシエチル)−1,2−エポキシシクロヘキサンおよび2,2−ビス(3 ,4−エポキシシクロヘキシル)プロパンなどのコネチカット州ダンベリーのユ ニオンカーバイド社(Union Carbide Corp.)製の脂環式エポ キシドの「登録商標ERL」シリーズが含まれる。好ましい脂環式ポリエポキシ ドは登録商標ERLシリーズである。 代表的な脂肪族ポリエポキシド(すなわち、炭素環を含有せず、2つ以上のエ ポキシ基を含有する化合物)には、1,4−ビス(2,3−エポキシプロポキシ )ブタン、グリセロール、ポリプロピレン グリコール、1,4−ブタンジオール等などの脂肪族ポリオールのポリグリシジ ルエステルおよびリノール酸のダイマー酸のジグリシジルエステルが含まれる。 多種多様な市販のエポキシ樹脂が利用可能であり、例えばリー(Lee)および ネビル(Neville)による、エポキシ樹脂ハンドブック(the Hand book of Epoxy Resins)、マグローヒル社(McGraw−H ill Book Co.)、ニューヨーク(1967年)、エポキシ樹脂、化学と技 術(Epoxy Resins,Chemistry and Technolog y)、第2版、メリー(C.Mary)編、マーセルデッカー社(Marcell Decker,Inc.)、ニュヨーク(1988年)およびエポキシ樹脂技術( Epoxy Resin Technology)、ブルーインズ(P.F.Br uins)編、インターサイエンス出版社(Interscience Publ ishers)、ニューヨーク(1968年)に掲載され、記載されている。そ こに記載されるエポキシ樹脂のいかなるものも本発明の半−IPNを製造する際 に有用となりうる。 必要に応じて、モノヒドロキシ−およびポリヒドロキシ−アルコールが、エポ キシ樹脂の鎖伸長剤として本発明の硬化可能な組成物に添加されてもよい。好適 なアルコールの例には、メタノール、エタノール、1−プロパノール、2−プロ パノール、1−ブタノール、1−ペンタノール、1−ヘキサノール、1−ヘプタ ノール、1−オクタノール、ペンタエリスリトール、1,2−プロパンジオール 、エチレングリコール、1,4−ブタンジオール、1,5−ペンタンジオール、 1,6−ヘキサンジオール、1,4−シクロヘキサンジメタノール、1,4−シ クロヘキサンジオールおよびグリセロールが含まれるがこれらに限定されない。 好ましくは、水酸基を含有す る化合物、特に約2〜50個の水酸基を含有する化合物、結局重量平均分子量が 約50〜25,000、好ましくは約50〜2000を有する化合物、例えばポ リエステル、ポリエーテル、ポリチオエーテル、ポリアセタール、ポリカーボネ ート、ポリ(メタ)アクリレート、および少なくとも2、一般には約2〜8では あるが、好ましくは約2〜4水酸基を含有するポリエステルアミド、またはこれ らの化合物の水酸基を含有するプレポリマーも本発明による代表的な有用な化合 物であり、例えばサウンダー(Saunders)著、高級ポリマー(High Polymers)、XVI巻、「ポリウレタン、化学と技術(Polyuret hanes,Chemistry and Technology)」、I巻、32 〜42ページ、44〜54ページおよびII巻、5〜6ページ、198〜99ペ ージ(1962年、1964年)、並びにクンスツトッフハンドブック(Kuns tstoff−Handbuch)、VII巻、45〜71ページ(1966年 )に記載されている。もちろん、少なくとも2つの水酸基を含有し、分子量が約 50〜50,000の上記化合物の混合物、例えばポリエーテルとポリエステル との混合物を使用することが許容される。 本発明によって使用するために好適な、少なくとも2つの反応性水酸基を含有 する低分子量化合物(分子量約50〜400)は、好ましくは水酸基を含有し、 一般には約2〜8個、好ましくは約2〜4個の反応性水酸基を含有する化合物で ある。また、少なくとも2つの水酸基を含有し、分子量が約50〜400の範囲 の異なる化合物の混合物を使用することが可能である。このような化合物の例は 、エチレングリコール、1,2−および1,3−プロピレングリコール、1,4 −および2,3−ブチレングリコール、1,5−ペンタンジオール、1,6−ヘ キサンジオール、1,8−オクタンジオー ル、ネオペンチルグリコール、1,4−シクロヘキサンジメタノール、1,4− シクロヘキサンジオール、トリメチロールプロパン、1,4−ビス−ヒドロキシ メチルシクロヘキサン、2−メチル−1,3−プロパンジオール、ジブロモブタ ンジオール(米国特許第3,723,392号)、グリセロール、トリメチロール プロパン、1,2,6−ヘキサントリオール、トリメチロールエタン、ペンタエ リスリトール、キニトール、マンニトール、ソルビトール、ジエチレングリコー ル、トリエチレングリコール、テトラエチレングリコール、高級ポリエチレング リコール、ジプロピレングリコール、高級ポリプロピレングリコール、ジブチレ ングリコール、高級ポリブチレングリコール、4,4’−ジヒドロキシジフェニ ルプロパンおよびジヒドロキシメチルヒドロキノンである。 本発明の目的のために好適な他のポリオールはヒドロキシアルデハイドとヒド ロキシケトンとの混合物(「ホルモース」)または触媒としての金属化合物と共触 媒としてエンジオールを形成することができる化合物との存在下においてホルム アルデヒド水和物の自己縮合の際に形成される、還元によって得られる多価アル コール(「ホルミトール」)である(例えば、German Offenlegun gsschrift第2,639,084号、同第2,714,084号、同第 2,714,104号、同第2,721,186号、同第2,738,154号 および同第2,738,512号を参照のこと)。 カルボワックス、ポリ(エチレングリコール)、ポリ(エチレングリコールメチ ルエーテル)、ポリ(エチレングリコール)、テトラヒドロフルフリルエーテル、 ポリ(プロピレングリコール)などの多官能性アルコールも本発明の組成物に使 用できることが考慮される。 本発明内のTHVとエポキシとの混合物は、半−IPNの製造を可能にする組 成物範囲を有する混和性ウィンドーを規定することができる。エポキシモノマー の添加時には、THV200の結晶開始点の降下は観察されなかった。融点降下 と共に観察される結晶点の降下は熱動力学的な部分混和を示す。部分混和は、狭 い範囲の条件にわたってだけ、すわわち組成物/温度/圧力が観察された均質な 溶液であったことを意味する。室温と200℃との間で測定した走査型示差測定 で示されるように、結晶化による発熱と融解による吸熱の領域は、THV/エポ キシ半−IPNのエポキシ含量が増加するにつれて減少した。これは、比較的低 かった(<20%)フルオロポリマーの結晶含量はエポキシモノマーの存在によ って悪影響を受けたことを明らかにした。エポキシモノマーのほとんどはTHV の(膨潤した)非晶質成分によって奪われると考えられる。 本発明のエポキシを硬化するための触媒は、熱的な手段または光化学的な手段 のどちらかによって活性化することができる。好ましい触媒は熱活性化される。 周知の光触媒には2つの大まかなタイプがある:オニウム塩およびカチオン有 機金属塩で、両者とも本発明に有用である。 カチオン重合のためのオニウム塩光開始剤には、ヨードニウムおよびスルホニ ウム錯塩が含まれる。有用な芳香族ヨードニウム錯塩は以下の一般式である: (式中、 Ar1およびAr2はは同じまたは異なり、炭素原子数4〜約20の芳香族基で あり、フェニル、チエニル、フラニルおよびピラゾリル基からなる群から選択さ れ; Zは酸素、硫黄、炭素−炭素結合、 (式中、Rは(フェニルなどの炭素原子数6〜約20の)アリール基または(ア セチルまたはベンゾイルなどの炭素原子数2〜約20の)アシル基である)、お よび(式中、R1およびR2は、水素、炭素原子数1〜約4のアルキル基および炭素原 子数2〜約4のアルケニル基からなる群から選択される)からなる群から選択さ れ; mは0または1であり;および Xは式DQn(式中、Dは元素の周期律表(ケミカルアブストラクト版)の第I B族〜第VIII族の金属または第IIIA族〜第VA族のメタロイドであり、 Qはハロゲン原子であり、nは1〜6の整数である)。好ましくは、金属は銅、 亜鉛、チタン、バナジウ ム、クロム、マグネシウム、マンガン、鉄、コバルト、またはニッケルであり、 メタロイドは好ましくはホウ素、アルミニウム、アンチモン、スズ、ヒ素および リンである。好ましくは、ハロゲン、Qは塩素またはフッ素である。好適なアニ オンの例は、BF4 -、PF6 -、SbF6 -、FeCl4 -、SnCl5 -、AsF6 -、SbF5OH-、SbCl6 -、S bF5 -2、AlF5 -2、GaCl4 -、InF4 -、TiF6 -2、ZrF6 -、CF3SO3 -、N(SO2CF3)2 -、およ びC(SO2CF3)3 -である。好ましくは、アニオンは、BF4 -、PF6 -、SbF6 -、AsF6 -、S bF5OH-およびSbCl6 -である。さらに好ましくは、アニオンは、SbF6 -、AsF6 -およ びSbF5OH-である。 Ar1およびAr2芳香族基は必要に応じて1つ以上の融合ベンゾ環(例えば、 ナフチル、ベンゾチエニル、ジベンゾチエニル、ボンゾフラニル、ジベンゾフラ ニル等)を有してもよい。望ましくは、芳香族基は、1つ以上の非塩基性基がエ ポキシドおよび水酸基官能基と本質的に反応しない場合には、それらで置換され てもよい。 有用な芳香族ヨードニウム錯塩は、参考として本明細書に組み入れられる米国 特許第4,256,828号により詳細に記載される。好ましい芳香族ヨードニ ウム錯塩は、(Ar)2I PF6および(Ar)2I SbF6である。 本明細書に有用な芳香族ヨードニウム錯塩は紫外スペクトル領域にのみ光感受 性である。しかしながら、それらは、周知の光分解可能な有機ハロゲン化合物の ための増感剤によって、近紫外および可視スペクトル範囲に増感してもよい。増 感剤の例には、参考として本明細書に組み入れられる米国特許第4,250,0 53号に記載されるような、芳香族アミンおよび着色芳香族多環式炭化水素が含 まれる。 本明細書に使用するために好適な芳香族スルホニウム錯塩開始剤は以下の一般 式である: (式中、R3、R4およびR5は同じであっても、異なってもよいが、ただしこれら の基のうちの少なくとも1つは芳香族である。これらの基は、炭素原子数4〜約 20の芳香族基(例えば、置換および未置換フェニル、チエニルおよびフラニル )および炭素原子数1〜約20のアルキル基からなる群から選択されてもよい。 「アルキル」という用語には、置換アルキル基(例えば、ハロゲン、アルコキシ およびアリールなどの置換基)が含まれる。好ましくは、R3、R4およびR5は 各々芳香族であり; Z、mおよびXは全てヨードニウム錯塩に関して上記に規定される通りである )。 R3、R4およびR5が芳香族基である場合には、必要に応じて1つ以上の融合 ベンゾ環(例えば、ナフチル、ベンゾチエニル、ジベンゾチエニル、ベンゾフラ ニル、ジベンゾフラニル等)を有しても良い。望ましい場合には、芳香族基は、 1つ以上の非塩基性基がエポキシドおよび水酸官能基と本質的に反応しない場合 には、それらによって置換されてもよい。 トリフェニルスルホニウムヘキサフルオロアンチモネートおよびp−(フェニ ル(チオフェニル)ジフェニルスルホニウムヘキサフルオロアンチモネートなど のトリアリール置換塩が好ましいスルホニウム塩である。有用なスルホニウム塩 は米国特許第5,256,828号により詳細に記載されている。 本発明に有用な芳香族スルホニウム錯塩は紫外スペクトル領域にのみ光感受性 である。しかしながら、米国特許第4,256,828号および同第4,250 ,053号に記載されるようなものなどの選択的な群の増感剤によって、近紫外 および可視スペクトル範囲に増感してもよい。 本発明に有用な好適な光活性可能な有機金属錯塩は、参考として本明細書に組 み入れられる、米国特許第5,059,701号、同第5,191,101号お よび同第5,252,694号に記載されているものを含む。有機金属カチオン のこのような塩は以下の一般式を有する: [(L1)(L2)Mm]+eX- (式中、 Mmは周期律表の第IVB族、第VB族、第VIB族、第VIIB族および第 VIII族の元素から選択される金属原子を示し、好ましくはCr、Mo、W、 Mn、ReおよびCoであり; L1は、置換および未置換非環状および環状不飽和化合物および基並びに置換 および未置換炭素環式芳香族および複素環式芳香族化合物からなる群から選択さ れる同じまたは異なるリガンドであってもよく、各々が金属原子Mの原子価殻に 2〜12個のπ−電子を寄与することができる、0、1または2つのリガンドを 示す。好ましくは、L1は置換および未置換η3−アリル、η5−シクロペンタジ エニル、η7−シクロヘプタトリエニル化合物並びにη6−ベンゼンおよび置換η6 −ベンゼン化合物(例えば、キシレン)からなる群から選択されるη6−化合物 並びに2〜4個の融合環を有する化 合物からなり、各々Mmの原子価殻に3〜8個のπ−電子を寄与することができ る群から選択され、 L2は、一酸化炭素、ニトロソニウム、トリフェニルホスフィン、トリフェニ ルスチビンおよびリンの誘導体からなる群から選択される同じまたは異なるリガ ンドであってよい偶数のπ−電子に寄与し、ただし、L1およびL2がMmに寄与 する総電子価が錯体の総残存正電荷となる0、1〜3個のリガンドを示し; eは1または2の値の整数で、錯体カチオンの残存電荷であり; Xは上記のように、ハロゲンを含有する錯体アニオンである)。 本発明の光活性可能な触媒として有用な有機金属錯体カチオンの好適な塩の例 には: (η6-ベンセンe)(η5-シクロペンタジエニル)Fe+1 SbF6 - (η6-トルエン)(η5-シクロペンタジエニル)Fe+1 AsF6 - (η6-o,p,またはm-キシレン)(η5-シクロペンタジエニル)Fe+1 SbF6 - (η6-クメン)(η5-シクロペンタジエニル)Fe+1PF6 - (η6-キシレン(混合異性体))(η5-シクロペンタジエニル)Fe+1 SbF6 - (η6-キシレン(混合異性体))(η5-シクロペンタジエニル)Fe+1 PF6 - (η6-o-キシレン)(η5-シクロペンタジエニル)Fe+1 CF3SO3 - (η6-m-キシレン)(η5-シクロペンタジエニル)Fe+1 BF4 - (η6-メシチレン)(η5-シクロペンタジエニル)Fe+1 SbF6 - (η6-ヘキサメチルベンゼン)(η5-シクロペンタジエニル)Fe+1 SbF5OH-お よび (η6-フルオレン)(η5-シクロペンタジエニル)Fe+1 SbF6 -. が含まれる。本発明に有用な有機金属錯体カチオンの好ましい塩には以下の1 つ以上が含まれる:(η6-キシレン(混合異性体))(η5-sシクロペンタジエニル)F e+1 SbF6 -,(η6-キシレン(混合異性体))(η5-シクロペンタジエニル)Fe+1 PF6 - ,(η6-o,p,またはm-キシレン)(η5-シクロペンタジエニル)Fe+1 SbF6 -,およ び(η6-メシチレン)(η5-シクロペンタジエニル)Fe+1 SbF6 -。 必要に応じて、有機金属塩開始剤に、第3アルコールのシュウ酸エステルなど の促進剤を併用してもよい。参考として本明細書に組み入れられる米国特許第5 ,252,694号に記載されるように、促進剤は好ましくは、総重合可能混合 物(熱可塑性成分、熱硬化性成分および触媒)の0.01〜10重量パーセント 、好ましくは0.1〜4重量%を含む。 有用な市販の開始剤には、FX−512、芳香族スルホニウム錯塩(ミネソタ 州セントポールの3M社(3M Company))、登録商標UVI−6974、 芳香族スルホニウム錯塩(コネチカット州ダンベリーのユニオンカーバイド社( Union Carbide Corp.)および登録商標IRGACURE26 1、カチオン有機金属錯塩(ニューヨーク州ホーソーンのチバガイギーケミカル ズ(Ciba Geigy Chmicals)が含まれる。 本発明に有用な光開始剤は、総硬化可能な樹脂組成物に対して0.01〜10 重量パーセント、好ましくは0.1〜5および最も好ましくは0.1〜2重量パ ーセントの範囲の量で存在してもよい。 エポキシ樹脂のためのある種の熱活性化硬化剤(例えば、化学反応に添加する ことによってエポキシドの硬化および架橋に影響を与える化合物)は本発明にお いて有用である。好ましくは、このような硬化剤は、成分を混合する温度におい て熱的に安定性である。 好適な熱硬化剤には、脂肪族および芳香族第1級および第2級ア ミン、例えばジ(4−アミノフェニル)スルフォン、ジ(4−アミノフェニル) エーテルおよび2,2−ビス−(4−アミノフェニルプロパン;脂肪族および芳 香族第3級アミン、例えばジメチルアミノプロピルアミンおよびピリジン;4級 アンモニウム塩、特にN−メチル−4−ピコリニウムヘキサフルオロホスフェー トなどのピリジニウム塩;参考として本明細書に組み入れられる米国特許第4, 684,678号に記載されるものなどのフルオレンジアミン; BF3・Et2OおよびBF3・H2NC2H5OHなどの3フッ化ホウ素錯体;メチルイミダゾー ルなどのイミダゾール:アジポヒドラジンなどのヒドラジン;並びにテトラメチ ルグアニジンおよびジシアンジアミド(DiCyとして通常周知の、シアノグア ニジン)などのグアニジンが含まれる。それらのうち多数は、高融点ポリオレフ ィン成分が存在する場合には、使用が不適当となることがあるので、これらの硬 化剤を注意深く選択すべきであるが、低融点ポリオレフィンおよびエポキシ樹脂 を含有する本発明の半−IPNを製造する際にはそれらは有用となりうることが 理解されるべきである。 高温エポキシ触媒は本発明に特に有用である。単純なピリジニウム、キノリニ ウム、ヨードレニニウム、ベンゾチアゾリウム、アルキル、アリールおよびアル キルアリールアンモニウムおよびホスホニウム塩が250〜350℃の範囲にお いてエポキシのカチオン重合の効果的な開始剤であることが見出されている。こ れらの高い発熱温度のために、これらの触媒は、例えばフルオロエラストマーの 200℃以上の高温の押出温度に使用するのに特に適している。この組成物は押 出器中で安定である、すなわちそれらは硬化しないので、この処理段階中の架橋 によって生じると思われる問題が排除される。最終的に硬化されると、これらの 組成物は驚くほど強い積層せん断接着強度を提供する。 一般に、カチオン窒素が中心に位置する塩はこの温度範囲において活性である 。驚くべき結果は、アニオンを変えて、カチオンを一定にした場合のこれらの化 合物シリーズの発熱温度の順序である。発熱温度 PF6 -<AsF6 -<SbF6 -の順に増加 する。エポキシ樹脂分野の当業者は順序がこの逆であるであろうと予測すると思 われる点において、これは驚くべきことである。 熱硬化剤として有用な塩の部類には、ピリジニウム、キノリニウム、ベンゾキ サゾリウム、ベンゾチアゾリウム、インドレニウム、アンモニウム、およびホス ホニウム塩が含まれる。エポキシ/ポリプロピレン組成物の触媒として特に好適 であることが見出されている塩の構造には以下が含まれる: (式中、Rはアルキル基またはアリール基であり、R’はアルキル基またはアシ ル基またはアリール基であり、R”はアルキル基ま たはアリール基であり、R'''はアルキル基またはアリール基である)。Rおよび R’が炭素原子数4〜8の環状構造を形成してもよい。(R、R’およびR''' が二環式環構造を形成してもよい。)アルキル基は炭素原子数1〜12を有して もよく、アリール基は1〜3の融合環(例えば、ナフタレン)または炭素原子数 30までの結合臭(例えば、ビフェニル)であってもよい。各カチオン電荷は適 当な数のアニオン、X-によって均衡を保たれるべきである。 また、ここでX-は先に規定するとおりであってもよく、好ましくはX-はBF4 - 、PF6 -、AsF6 -、SbF6 -またはCF3SO3 -であり、最も好ましくはX- はPF6 -である。 ここで、各R、R’、R”、R'''は独立して炭素原子数20までのアルキル 、アリールまたはアルカリル基であってもよく、Xは先に規定されるとおりであ る。 熱硬化剤は、熱エポキシ硬化剤当量に対するエポキシ当量の比が0.9:1〜 2:1の範囲にあるような量で存在してもよい。 熱硬化は、熱可塑剤が結晶化する前または結晶化してから実施してもよい。ほ とんどの可能な用途において、フィルムが最終製品に製造される準備ができるま でフィルムを硬化する必要はない。熱可塑剤の分子配向が保存される必要がある 場合には、インラインでの硬化が望ましいことがある。 硬化後の半−IPNの物理特性を変えるために、種々の補助剤を本発明の組成 物に添加することもできる。有用な補助剤には、ヒュームシリカなどのチキソト ロピー剤;酸化第二鉄、カーボンブラックおよび二酸化チタンなどの色調増強顔 料;雲母、シリカ、炭酸カルシウム、硫酸マグネシウムおよび硫酸カルシウムな どのフィラー;ベントナイトなどのクレー;ガラスビーズおよびバブル;ポリエ ステル、ポリイミド、ガラスファイバー、ポリ(p−フェニレン テレフタルアミド)などのポリアミド、炭素繊維およびセラミック繊維などの有 機および無機繊維の単方向職および不織ウェブなどの強化材料が含まれる。10 0部のポリオレフィン−エポキシ組成物あたり約200部までの補助剤が使用さ れてもよい。 上記の添加剤および補助剤に加えて、フルオロポリマー樹脂とエポキシ樹脂と の混合物中にポリオレフィンおよびポリアミドの一方または両方を添加すること は本発明の範囲内である。 本明細書において使用される「ポリオレフィン」は好ましくはカチオン、アニ オン、またはジーグラー−ナッタ(Ziegler−Natta)−型重合過程 によって炭化水素オレフィンモノマーのホモ重合および/または共重合から製造 された、有機官能基を本質的に有しない十分に予備重台されたポリマー炭化水素 をいう。本明細書に有用なホモポリマーポリオレフィンには、ポリエチレン、ポ リプロピレン、ポリ−1−ブテン、ポリ−1−ペンテン、ポリ−1ヘキセン、ポ リ−1−オクテンおよび関連するポリオレフィンが含まれる。好ましいホモポリ マーポリオレフィンには、ポリエチレン(例えば、登録商標Dow25455、 ミシガン州ミッドランドのダウ ケミカル社(Dow Chemical Co. )製)およびポリプロピレン(例えば、登録商標Shell DS5D45、テ キサス州ヒューストンのシェルケミカルズ社(Shell Chemicals ,Inc.)製または登録商標Exxon3445および登録商標3505、テ キサス州ヒューストンのエクソンケミカルズ(Exxon Chemicals )製)が含まれる。ポリ(エチレン−コ−プロピレン)(例えば、登録商標SR D7−462、登録商標SRD−463および登録商標DS7C50、各々シェ ルケミカルズ社(Shell Chemicals,Inc.)製)、ポリ(プロ ピレン−コ−1−ブテン)(例えば、登録商標SRD6 −328、シェルケミカルズ社(Shell Chemicals,Inc.)製 )および関連するコポリマーを含む、これらのα−オレフィンのコポリマーも有 用である。好ましいコポリマーはポリ(エチレン−コーポリエチレン)である。 ニュージャージー州ピスカタウェイのヒュールスアメリカ社(Huls Ame rica Inc.)製の登録商標Vestoplastシリーズのポリオレフィ ンも有用である。 本発明に有用なポリオレフィンは、ポリオレフィンに対するフルオロポリマー の比が1:99〜99:1、好ましくは25:75〜75:25、最も好ましく は50:50の範囲内にあるような量で存在してもよい。ポリオレフィンとフル オロポリマーとの混合物が存在する場合には、エポキシ樹脂成分は好ましくは、 ポリオレフィン:フルオロポリマーの全ての比に対して、混合物の総重量の約1 0〜約15重量%を含む。 本明細書において使用する「ポリアミド」は、ポリマー骨格中のアミド基、− CONH−の存在によって特徴づけられる、十分に予備重合された縮合ポリマーをい う。ポリアミドは、例えばジカルボン酸またはジカルボン酸ハライドなどの多官 能性カルボキシル−含有種と多官能性アミンとの縮合重合によって、またはアミ ン−およびカルボキシル−官能基を共に有する2官能性分子の自己縮合によって 製造される。反応性種は独立に脂肪族、芳香族、炭素環式、多環式、飽和、不飽 和、直鎖または分岐鎖であってもよい。ポリアミドは1つの多カルボキシル官能 性種と1つのポリアミン種との重合生成物てあっても、並びに多カルボキシル種 の混合物とポリアミン種の混合物との重合生成物であってもよい。業界は多数の ポリアミド経路を開発しており、その全ては本発明の規定内に含まれることが意 図される。「ナイロン」として周知の大まかな部類のポリアミド は市場では最も豊富に出現するが、本発明の規定はそれに限定されることを意図 していない。本発明のために好ましいポリアミドには、デラウェアー州ウィルミ ントンのデュポン社(DuPont Co.)製のNylon6、Nylon66 、Nylon12およびNylon材料の群並びにペンシルバニア州アンブラー のヘンケル社(Henkel Corp.)製の登録商標Versamide群の ポリアミドが含まれる。 本発明に有用なポリアミドは、ポリアミドに対するフルオロポリマーの比が1 :99〜99:1、好ましくは25:75〜75:25、最も好ましくは50: 50の範囲内であるような量で存在してもよい。ポリアミドとフルオロポリマー との混合物が存在する場合には、エポキシ樹脂成分は好ましくは、ポリアミド: フルオロポリマーの全ての比に対して、混合物の総重量の約10〜約15重量パ ーセントを含む。 フルオロポリマー−エポキシ半−IPNは保護被覆、接着剤、自己支持フィル ムとして多層集成物において有用である。最も好ましくは、本発明の半−IPN は金属、プラスチック、ガラスまたはセラミックのための構造接着剤として;自 己支持型ホットメルト接着剤として;または保護被覆として有用である。好まし い実施態様において、フルオロポリマー−エポキシ半−IPNを可撓性基材に被 覆して接着テープを製造することができる。特殊な用途において、半−IPN被 覆とフィルムを電気ケーブルおよびコミュニケーションケーブルのための多層集 成物中に存在することができる。別の好ましい実施態様において、フルオロポリ マー−エポキシ半−IPNを、ガソリンなどの炭化水素燃料の貯蔵または輸送に 使用される、ポリマー、好ましくはポリオレフィン、さらに好ましくはポリプロ ピレンタンクまたは容器に被覆することができ、本発明の半−IP Nはポリオレフィン容器と結果として生じるフルオロポリマー(例えば、ポリ( テトラフルオロエチレン)(PTFE))保護被覆との間の結合剤として作用する 中間(または「結合」)被覆となりうる。本発明の半−IPNはまた、腐食製化学 物質の輸送および貯蔵に使用される金属タンクまたは溶液の内部被覆としての直 接的な用途が見出される。 本発明の目的および利点は以下の実施例によってさらに例示されるが、これら の実施例に引用される特定の材料およびその量並びに他の条件および詳細は本発 明を不用意に限定すると解釈されるべきではない。 実施例 試験手順 引張り係数、引張り強度 5KNロードセル、型番2511−317を装備したインストロン(Inst ron)引張り試験装置(インストロン社(Instron Corp.)、イリノ イ州パークリッジ)を使用して、引張り係数および引張り強度を測定した。クロ スヘッド速度およびゲージ長さは、示すように各試験で変えた。 積層せん断;ピーク負荷 積層せん断測定値は、本質的に、ASTM D1002−94、「シングル− ラップ−ジョイント接着金属試料の引張り負荷によるみかけのせん断強度(Ap parent Shear Strength of Single−Lap−Jo int Adhesively Bonded Metal Specimens by Tension Loading)」によって得た。11.43cm×2. 54cm×3.2mmの冷たいロール型スチール銅切取試片をメチルエチルケト ンで十分に洗浄して、ホットプレート上で約185〜約250℃まで加熱した。 約0.25および0.75の厚さを有するフィルムを、シリコンゴムローラーを 使用して熱い金属表面に適用し、融解させた。光触媒を含有するフィルムを融解 しながら、TLD15W/03(フィリップス(Phillips)、オランダ) または350BL(ジーメンズ社(Siemens Corp.)/オスラムシル バニア社(Osram Sylvania Inc.)、マサチューセッツ州ダン バーズ)UV−放射ランプによる3.1J/cm2の放射エネルギーに暴露させ た。2つの硬化後の半分を、登録商標Scotchkote134Epoxy( 3M社(3M Company)、ミネソタ州セントポール)によってフィルム側 同士を接着した。積層面積は2.54cm2であった。185℃において、非常 に薄い登録商標Scotchkoteを1つの半分にのせ、もう半分をその上に のせた。試験するフィルム片を2つの切取試片の間に225℃において5分間配 置することによって熱硬化システムを含有する試料を製造した。次いで試料に加 熱することをやめ、22℃まで冷却した。44.5KNロードセルを装備したイ ンストロン(Instron)装置によりピーク負荷と破壊歪みを記録した。 誘電率 本質的に、カイズリー(Keithly)237および8008抵抗固定およ び500ボルト、相対湿度45%での60秒帯電時間を使用してASTM D2 57−93により誘電率の測定値を測定した。HP16451B誘電率試験固定 装置(Dielectric Test Fixture)(カリフォルニア州パ ロアルトの ヒューレット−パッカード社(Hewlett−Packard Co.)を装備 したHP4284Aプレジション(Precision)LCRメーターを用い て500mHzの測定値を測定した。HP16451A誘電率試験固定装置(D ielectric Test Fixture)を使用して、HP4291Aイ ンピーダンス/マテリアルアナライザー(Impedance/Materia l Analyzer)を用いて900mHzの測定値を測定した。 実施例1 少なくとも2つの方法で組成物を製造することができる。方法Aでは、乾燥し た脱フッ化水素化登録商標THV200粉末を、熱可塑性ポリマー成分の総重量 に対して、2〜10重量パーセントの登録商標PR500と共にシグマブレード を装備し、予備加熱したブラベンダー(Brabender)インターナルミキ サー内で185℃で混合した。次いで試料を望ましい厚さにメルトプレスした。 脱フッ化水素化の詳細は米国特許第3,507,844号、同第4,758,6 18号および米国特許同時係属出願番号第08羽703,422号を参照のこと 。 方法Bでは、ツインスクリュー押出装置を使用してフィルムを製造した。登録 商標PR500(エポキシとフルオレンアミン硬化剤との混合物を含有する)を 、フルオロポリマーペレット供給ポートの側面ポート下降流によって添加した。 スタティックミキサーおよび15.2cm(6”)シートダイを装備したハーケ (Haake)カウンター−回転式円錐ツインスクリュー押出器(31.8/2 0mm(後方/前方)中で90rpmのスクリュー速度で試料を押し出した。供 給部からダイまでの温度プロフィール(℃)は86−9 2−92−86であった。テイクアップホイールは25℃に維持した。ライン速 度は30.5cm/分(1ft/分)で、押出物の厚さは381マイクロメータ ー(15mil)であった。 誘電特性および接着特性 半−IPNでは熱硬化剤の硬化の際の熱可塑剤の物理状態は特殊な硬化特性を 開発するのに重要である。 金属上への積層または接着はUVまたは熱硬化を使用して実施される。接着を 生じさせるためには、基材を熱可塑剤の融点より高く加熱し、次いで照射するこ とが必要とされる。熱硬化システムの最小サイクルは225℃において5分であ った。試料上に5分間2.54cm(1”)配置される場合には、Sylvan ia350BLバルブ(ジーメンズ社(Siemens Corp.)/オスラム シルバニア社(Osram Sylvania Inc.)、マサチューセッツ州 ダンバーズ)を使用してもよい。室温での暴露後に、ガラス転移温度を好ましく は熱硬化相において150℃以上まで増すために、その後高温でのオーブン硬化 が必要である。放射線量が2〜3J/cm2の間である限りは、融解ランプを使 用してもよい。次いで熱源から試料を取り出し、室温まで冷却した。積層せん断 試験を使用して、室温における接着性を調べた。表1のデータは、熱硬化剤の硬 化の際に熱可塑剤を融解したときに得られた接着特性を示す。 表1のデータは、異なる組成物で見られる弾性率の増加を示す。掲載した引張 り特性は、室温において融解ランプによる硬化する、すなわち、熱可塑剤が固体 状態にあったときに硬化することによって得られるものである。熱硬化剤の硬化 の際に熱可塑剤が融解しなかった場合には低接着性が生じた。引張り係数の増加 は、熱可塑剤が結晶化した後に硬化が生じたときに観察された。 UV硬化および熱硬化共に、脱フッ化水素化を実施しない場合に同じような積 層せん断強度値を示した。脱フッ化水素化は約11.6MPaまで積層せん断強 度を増加した。接着性の同じような値はTHV/立体規則的(stereore gular)−ポリオレフィン/エポキシシステムで得られた。脱フッ化水素化 されたものを含む、THV/エポキシ半−IPN試料は接着しなかった。THV /ポリオレフィンエポキシおよびポリオレフィン/エポキシ半−IPNは粘着し なかった。 THV/エポキシシステムに立体規則的(stereoregular)ポリ オレフィンを追加すると、引張り強度も増加した。これはまさに相分離微小構造 であると考えられる。軟らかいマトリックス内への硬い添加物の結果として延仲 性が低下した。THV/ポリオレフィン/エポキシ押出物は外観が非常に良好で 、押出が容易であった。DS7C50はゴム相含量が20%のポリプロピレンで あった。ゴム相は完全に飽和させたエチレン(55%)プロピレンコポリマー( 45%)であった。ポリプロピレンホモポリマーに対 するゴムの分子量比は1:5であった。ポリプロピレン中のゴム含量がこのよう であることによって、THV/ポリオレフィン/エポキシ半−IPNに最適な接 着特性が提供される。 実施例2 THV半−IPN被覆およびフィルムの用途は電気ケーブルおよびコミュニケ ーションケーブルの多層集成物中であってもよい。 電気的な集成物中では、誘電強度、誘電定数および誘電損失などの特性を、本 発明の半−IPNの有用性を測定するために使用することができる。先に記載し た硬化後のTHV200/エポキシ半−IPNについてのこれらの測定の結果を 表2に示す。 表2のデータは、10重量パーセント未満のポリオレフィン(DS7C50) またはマレイン酸化ポリオレフィン(登録商標EpoleneG3003)を混 合することは、誘電定数または誘電損失に影響を与えることなく、THV200 の誘電強度を有意に増加することを示す。比較的高量の50重量パーセントのD S7C50ポリオレフィンを添加する際には、誘電強度はさらに有意に増加され たが、誘電定数と誘電損失はともに有意に低下した。比較として、ASTM D 149−94を使用して評価した、配向されていないプラスチックの最も短い期 間の誘電強度は架橋ポリ塩化ビニルにおいて1.5kV/25.4マイクロメー ターであることが観察された。比較的少量のカチオン硬化芳香族エポキシ(試料 2B)を添加することにより、THV200の誘電強度に影響を与えることなく 、誘電定数および誘電損失の両方をかなり低下したこと注目される。 実施例3 本発明のエポキシ−フルオロポリマー半−IPNを押出法によって製造した。 フルオロポリマー、エポキシ樹脂および触媒を、押出器の中にモノマーを流入さ せるために、キャパシティ0.16mL/ターンのゼニス(Zenith)HP Bギアポンプを装備したハーケ(Haake)円錐ツインスクリュー押出器中で 混合した。押出器中の温度硬化点は271℃において全てが硬化され、実際のゾ ーン温度は一般に234−273−271−271℃であった。6試料を調製し た: 上記の表3において、FEP−100はデラウェアー州ウィルミントンのデュ ポン社(DuPont Co.)製のポリ(テトラフルオロエチレン−コ−ヘキサ フルオロプロピレン)であり;EP−610は日本のダイキン(Daikin) 社製のポリ(エチレン−コーテトラフルオロエチレン)であり;Kynar74 0はペンシルバニア州フィラデルフィアのエルフ アトケム(Elf Atoc hem)社製のポリ(フッ化ビニリデン)で、MPは(実施例6のように調製し た)N−メチル−4−ピコリニウムヘキサフルオロホスフェートであった。 基材上に押出物(10.16cm×2.54cm)を配置し、この構成物を2 71℃までの温度で5分間加熱することにより、約380マイクロメーターの試 料を、スチール鋼、ポリアミドフィルムおよび登録商標Teflonフィルム基 材との接着性について定量的に試験した。試料3Dおよび3Fはスチール鋼との 限界接着性を示したが、ポリアミドまたはTeflonに対してはどれも示さな かった。試料3A、3B、3Cおよび3Eはこれらの条件下でもいかなる基材に 対しても接着性を示さなかった。 同様に、第2のセットの試料を基材の各々に適用し、271℃において15分 間加熱した。この場合も、試料3Dおよび3Fはスチール鋼との接着性を示した 。試料3Bはスチール鋼よりTeflonに対してわずかに大きい接着性を示し たが、全ての他の試料はTeflonに対する接着性を示さなかった。試料3S および3Fはポリアミドフィルムに弱冠の接着性を示した。 スチール銅に対する試料3Dの接着性をさらに以下に示す。15×2.54× 0.03cmの5枚の帯状の試料3Dを11.4×2.54×0.03cmのス チール鋼のバー上に配置し、299℃において15分間加熱した。冷却時に、ス チール銅のバーをインストロン(Instron)装置の一方のクランプに配置 し、他方のクランプに過剰の試料のフィルムを配置して、180°の剥離試験を 測定することにより、剥離値を得た。7.62cmのゲージ長さを使用し、クロ スヘッド速度は5.08cm/分であった。データを以下の表3bに示す。 表4に示すように、試料3A〜Fの引張り特性を得た。押出器から直接受け取 る、「未硬化」状態および試料を271℃において5 分間加熱することにより「硬化」した状態で各組成物を調べた。表4に報告する 値は周囲温度(約23℃)で得られた;ゲージ長さは2.54cmでクロスヘッ ド速度は5.08cm/分であった。値は記録したデータあたり5試料に対して 報告する。 表4のデータは、フルオロポリマーの引張り特性はエポキシ樹脂と硬化剤との 混合によって悪影響されないことを示す。 実施例4 THV200および3.4重量%のERL−4221エポキシ樹脂(シェルケ ミカルズ社(Shell Chemicals,Inc.)、テキサス州ヒュースト ン)を含有する半−IPN構成物を、温度プロフィールが192−222−22 1−219℃でペレットの供給速度が14.2g/分の押出器で調製した。キャ ストホイールは20℃に維持し;ライン速度設定は25であった。トリアリール スルホニウムヘキサフルオロホスフェート(FX−512活性化エポキシ硬化剤 、3M社(3M Company)、ミネソタ州セントポール)触媒濃度は1重 量%であった。 結果として得られた、10.2cm×2.54cm×0.0254cmの押出 フィルムの一方の部分を2片のポリ(エチレンテレフタレート)(PET)剥離ラ イナー(登録商標Scotchparポリエステルフィルム、3M社(3M Co mpany)、ミネソタ州セントポール)の間に配置した。同じ寸法の第2の部 分を、米国特許第4,822,451号、実施例5に記載するように、予めUV 線照射で処理しておいた2片のPET剥離ライナーの間に配置した。2つの試料 を190℃のホットプレート上に配置し、1cmの距離において5分間シルバニ ア(Sylvania)350ブラックライト(Blacklight)UV発 生バルブ(ジーメンズ社(Siemens Corp.)/オスラムシルバニア社 (Osram Sylvania Inc.)、マサチューセッツ州ダンバーズ) で照射した。照射後の試料を冷却し、1.27cm×10.2cmの帯状に切断 し、次いでクロスヘッド速度1.27cm/分およびゲージ長さ2.54cmの インストロン(Instron)引張り試験装置(型番1122)を使用してラ イナーに対する接着性について試験した。 未処理PETライナーの最小負荷:0.0092MPa UV処理PETライナーの最小負荷:0.0070MPa データは、本発明のエポキシーフルオロポリマーは業界で普通に使用される剥離 ライナーに対してでも中等度の接着性を示すことができることを示す。 実施例5 THV500フルオロポリマーと対応するポリマーとの配合物を含有する本発 明の半−IPNを、上記のようにツイン−スクリュー押出器中で調製した。配合 物の組成を表5に示す。 実施例5A〜5Eは、以下のポリマーフィルムと接触させながら、1cmの距離 で5分間UV照射下(シルバニア(Sylvania)ブラックライトバルブ) においてテフロンで覆ったホットプレート上で185℃において加熱した: 1.PET剥離ライナー(登録商標Scotchparポリエステルフィルム ) 2.登録商標ポリオレフィン1150−1(イーストマンケミカルズ(Eas tman Chemicals)、テネシー州キングスポート) 3.登録商標Elvamide8064ナイロンフィルム(デュポンケミカル 社(DuPont Chemical Co.)、デラウェアー州ウィルミントン) 4.登録商標Tenite1550Pポリエチレン(イーストマンケミカルズ 社(Eastman Chemicals Co.)中5%登録商標Epolen e(C18)イーストマンケミカルズ(Eastman Chemicals) 5.登録商標Exact4038ポリオレフィン、メタロセン触媒(エクソン ケミカル 社(Exxon Chemical Company)、テキサス州ヒ ューストン) 6.25%登録商標ERL−4221エポキシ樹脂(ユニオンカーバイド社( Union Carbide Corp.))と混合した登録商標Exxon344 5プロピレンホモポリマー(エクソンケミカル社(Exxon Chemical Company)) 6つのフィルムに対する本実施例のエポキシ−ポリマー配合半−IPNの接着 性を以下のように定性的に観察した: 実施例5A〜5EはPET(フィルム1)およびナイロン(フィルム3)に対 する接着性を示した: 実施例5Bもワックス添加ポリエチレン(登録商標Tenite1550P) (フィルム4)およびメタロセンポリオレフィン(フィルム5)に対する接着性を 示した; 実施例Cもポリオレフィン1150−1(フィルム2)、メタロセンポリオレフ ィン(フィルム5)およびポリプロピレン−エポキシ(フィルム6)に対する接 着性を示した。 実施例5のデータは、ナイロンまたは官能性ポリオレフィンと本発明のTHV −エポキシ半−IPNとの硬化後の配合物は多数のポリマー基材に良好な接着性 を示したことを示す。この配合物は、ポリエチレンなどのポリマー基材に保護被 覆を接着しやすくするために、多層ポリマー構造物中の結合層として有用となり 得る。 実施例6 N−メチル−4−ピコリニウムヘキサフルオロホスフェート触媒(触媒MP) を以下のように調製した: 50gの4−ピコリン(アルドリッチケミカル社(Aldrich Chem ical Co.)と76.2gのインドメタン(アルドリッチケミカル社(Al drich Chemical Co.)との600mL1,2−ジクロロメタン 溶液を約23℃の室温で攪拌した。わずかに反応が発熱した後、沈殿が形成し、 混合物を約3時間攪拌し、室温まで冷却した。固形の生成物をろ過により回収し 、2×250mLの1,2−ジクロロメタン、2×250mLの石油エーテルで 洗浄し、空気乾燥し、次いで50℃のオーブンで減圧下 において一晩乾燥した。オフホワイトの固形物、4−メチル−4−ヨウ化ピコリ ニウム(106g)を得た。 35gのN−メチル−4−ヨウ化ピコリニウムの200mL水溶液を、予め最小 量の水に溶解しておいた24.3gのヘキサフルオロリン酸アンモニウム(アル ドリッチケミカル社(Aldrich Chemical Co.)で処理した。 2種の溶液を混合したとき、沈殿が形成した。ろ過して沈殿を回収し、2×10 0mLの水で洗浄し、吸引乾燥し、次いで40℃の減圧オーブン内で一晩乾燥し た。総量30gの白色固形のN−メチル−4−ピコリニウムヘキサフルオロホス フェートを得、示差走査熱量測定法によりmp.210°であった。生成物の同 定はIRおよびNMR分光計によって確認した。 本発明の範囲および精神から逸脱することなく、本発明の種々の修正および変 更を加えることは当業者に明らかとなり、本発明は本明細書に記載する例示的な 実施態様に不用意に限定されるべきではないことが理解されるべきである。DETAILED DESCRIPTION OF THE INVENTION Fluoropolymer-epoxy resin semi-interpenetrating network composition Technical field   The present invention relates to the use of the present invention in the presence of a fully prepolymerized thermoplastic fluoropolymer. Prepared by polymerizing a thermosetting resin (ie, an epoxy resin), Semi-interpenetrating polymer network structure of thermoplastic resin and thermosetting resin (semi-IPN) About. The invention also relates to the treatment of 100% solids and the latent curing of epoxy resins. Or a method for producing a semi-IPN, characterized by post-curing, and by this method Provide the manufactured semi-IPN. Background art   Curable thermoset to make the cured product tough (ie, to increase ductility) It is industrially common to mix small amounts of elastomeric or thermoplastic materials with Is to be implemented. Natural rubber for elastomer or thermoplastic curing agents , Polyolefins and poly (styrene-co-butadiene). This In such a case, the thermoplastic composition becomes a dispersed phase in the thermosetting resin and becomes a continuous phase. As such, the curing agent is formulated in a ratio of about 1:20 to about 1: 4. For example, US Pat. , 861,647 and 5,008,135.   Solvent-based formulations of fluoropolymers and thermosets provide corrosion protection. U.S. Pat. No. 3,784,506 as useful as a coating for metal substrates for And 4,179,542. These coatings are separated from the solid resin Ball mill or High shear mixing, and then disperse the metal substrate, typically by spray coating. It is formed by applying the powder and then heating at a temperature up to 250 ° C. A coating of 100% solids semi-IPN is not described.   Photoinitiated cationic polymerization of epoxides is well known. Organic aryl sulfonium And aryl iodonium salts are suitable photoinitiators, i.e. For example, it is recognized as a compound that releases a proton that initiates epoxide polymerization. Certain metal-allene organometallic complexes also act as photoinitiators for cationic polymerization. It is described. In these cases, the cationically polymerizable component is a monomer. Disclosure of the invention   Briefly, the present invention is a curable composition comprising: a) a curable epoxy resin; b) an effective amount of a curing agent for the curable epoxy resin; c) a fully prepolymerized uncrosslinked fluoropolymer; d) if necessary, with polyolefin or polyamide And a solvent-free composition.   Preferably, the epoxy component comprises from 0 to 75 weight percent of the total composition. And more preferably from 0 to 70 weight percent, even more preferably 0 To 40 weight percent, most preferably 0.5 to 15 weight percent. And the fluoropolymer is present in an amount ranging from 25 to 100% by weight relative to the total composition. Percent full, more preferably less than 30 to 100 weight percent, more More preferably less than 60 to 100 weight percent, most preferably 85 to 9 Present in the range of 5.5 weight percent. The composition is preferably an epoxy resin after curing. Includes a curing agent that physically incorporates fluorine into the skeleton No.   In another embodiment, the present invention relates to a thermoset and / or photochemically cured epoxy resin. Semi-interpenetrating polymer network containing fully prepolymerized fluoropolymer Describe the structure.   In another aspect, the present invention relates to a method for producing a semi-IPN, comprising: A photochemical or heat-curable epoxy resin in the absence of a medium; and For this epoxy resin, only a few light curing agents or high temperature stable Polyolefins, preferably both uncrosslinked in the presence of at least one And / or polyamide, if necessary, to ensure Mixing and mixing the combined fluoropolymers, and (b) optionally Applying a solvent-free mixture to the substrate, and (c) optional mixing after mixing. Providing sufficient heat and / or light energy to the mixture over time; Activating a curing agent or photocatalyst. You.   In yet another embodiment, the presence of a polyolefin or polyamide In the presence, the fluoropolymer is defluoridated before being combined with the epoxy monomer. The semi-IPN provided by the priming has an increased adhesiveness to the substrate.   Although not previously described in the art and provided by the present invention, Can be cured in the presence of polyolefins or polyamides if required. Functional thermosetting resin, that is, epoxy resin and its curing agent, if necessary A curable epoxy resin containing a fully prepolymerized fluoroelastomer Fat is used as a curing agent for ArThreeSSbF6(In the formula, “Ar” represents, for example, phenyl or the like. The presence of a suitable onium salt photoinitiator, such as aromatic species) or fluorenamine. In the presence, on the spot, molded into a useful form, Until coated or manufactured, curing conditions, i.e., irradiation with light, preferably Or solvent-free compositions that are preferably not exposed to temperatures above about 170 ° C. It is. Other curing agents allow for processing at higher temperatures.   Fluoropolymer-epoxy semi-IPNs are used as protective coatings, adhesives and many more. Useful in layer assemblies. More particularly, the semi-IPN of the present invention comprises As a structural adhesive for plastics or ceramics; Useful as adhesives; or as protective coatings. In a preferred embodiment Fluoropolymer-epoxy semi-IPN coated on a flexible substrate and adhesive tape Can be manufactured. In a further preferred embodiment, the fluoropolymer -Epoxy semi-IPN for storage or transportation of hydrocarbon fuels such as gasoline And preferably contains a polyolefin, more preferably a polyolefin. Pyrene-containing polymer tanks or containers can be coated, -The IPN comprises a polymer container and the resulting fluoropolymer (eg, poly Acts as a binder between (tetrafluoroethylene (PTFE)) protective coating It may be an intermediate (ie, “bonded”) coating. The semi-IPN of the present invention is Metal tanks or containers used to transport and store volatile chemicals. Direct applications are also found.   In this application:   "Epoxy resin" means a curable material, including mono- and polyepoxides. Including;   "Backbone" means the polymer backbone and does not include side groups or terminal groups;   A "cationic organometallic salt" is a salt, at least one of an organic group bonded to a metal atom. Means a cation moiety containing a carbon atom. Basic Inorganic Chemistry ", cotton (F. A. cotton), Wilkinson (G. Wilkinson), Willey (W iley), New York, 1976, p497); preferably a metal atom Is a transition metal atom;   A "group" is a conventional moiety that does not interfere with the species that permits substitution or the desired product. Refers to a chemical species that may be substituted by a substituent, for example, a substituent It may be enyl, halo (F, Cl, Br, I), cyano, nitro and the like.   "Semi-interpenetrating polymer network (semi-IPN)" refers to at least one polymer Are crosslinked and at least one polymer is uncrosslinked. Meaning rimer network structure,   "Fluoroelastomer" has a high tensile strength, Shrinks to its original dimensions and fully deforms, when deformed to the limit, Has the properties of natural or synthetic rubber in that Means a fluorinated polymer that does   “Fluoropolymer” or “fluorocarbon polymer” has at least one At least half of the hydrogen atoms made from the species monomer and directly attached to the carbon atom Means a polymer in which is replaced by a fluorine atom;   "Dehydrofluorination" separates HF from fluorocarbon units of the polymer, Means to produce unsaturated units during the limer; and   "Curing agent", "Curing agent", "Catalyst" and "Initiator" affect the polymerization reaction Used to mean any active or reactive species used to replace It is possible.   The semi-IPN of the present invention is characterized in that the fluoropolymer component has electrical properties and chemical properties. That it can contribute to the Nomer components may contribute to stability, composition flexibility and composition post-curability. It has advantageous properties in that it can. Detailed Description of the Preferred Embodiment   The present invention is a curable composition comprising: a) a curable epoxy resin; b) an effective amount of a curing agent for the curable epoxy resin; c) a fully prepolymerized uncrosslinked fluoropolymer and optionally a polyole With fins or polyamide A composition comprising:   Preferably, the combination of components is at a temperature below the thermal activation temperature of the catalyst, ie, 170 ° C or higher, preferably in the range of 170 to 400 ° C, more preferably 200 to 400 ° C. It occurs at temperatures in the range of ° C.   Useful fluoropolymers can be made by methods well known in the art, For example, Dyneon L.C., St. Paul, Minn. LC) manufactured by THV200, THV230, THV500, THV 530, registered trademark Fluorel (HFP / VDF), registered trademark Fluorel- II (TFE / PP / VDF) and registered trademark Kel-F800, fluoroelastomer Stomer; Elf Atochem N. America Orth America Inc. (Philadelphia, PA) Trade name registered trademark Kynar740, 2800, 9301; Kureha Chemical Co. (K ureha Chemical Co.) KF polymer; Daikin America, Inc. (New York) (New York) trade name Neofluoron VDF; Central Gala (Central Glass), Tokyo, Japan, trade name registered trademark Cefra l SoftG-150 and Asahi Glass Co., Ltd. Co. , Ltd. ) (AFLAS200 trade name registered trademark, manufactured by Tokyo, Japan) You may.   In a further preferred embodiment, the fully prepolymerized fluoropolymer is Of tetrafluoroethylene, hexafluoropropylene and vinylidene fluoride Terpolymer (hereafter referred to as THV, Dyneon & St. Paul, Minn.) Luelcy (Dyneon LLC)). Most preferably, THV20 0 (42 mole percent TFE, 20 mole percent HFP, 30 mole percent VDF). The terpolymer backbone contains units derived from the following monomers: Have.   THV and others in addition to those mentioned above, fluoropolymers that may be useful in the present invention Generally include tetrafluoroethylene, chlorotrifluoroethylene, Such as fluoropropylene, vinylidene fluoride and perfluoropropyl vinyl ether Which group contains perfluoroalkyl vinyl ether and trifluoroethylene And homopolymers and copolymers made from. For special polymers , Poly (ethylene-co-chlorotrifluoroethylene) (ECTFE), poly (te Trafluoroethylene) (PTFE), poly (tetrafluoroethylene-co-hex) Safluoropropylene (FEP), poly (ethylene-co-tetrafluoroethylene) (ETFE), poly (ethylene-co-tetrafluoroethylene-co-hexaf) Fluoropropylene) (EFEP), poly (vinylidene fluoride) (PVDF) and Including, but not limited to, poly (chlorotrifluoroethylene) (PCTFE). Not determined. Of course, numerous other fluoropolymers that may be useful in the present invention are It is well known in the art.   In another embodiment, an epoxy monomer and optionally a polyolefin or By dehydrofluorinating the fluoropolymer before combining with the polyamide And a semi-IPN having increased adhesion to a substrate. Combined with the semi-IPN of the present invention Of the fluoropolymer Dehydrofluorination can provide desirable adhesion properties to a substrate. H The mole percent of dehydrofluorination present in the fluoropolymer is from 0.01 to 20. Range, preferably 0.01 to 5.0, more preferably 0.02 to 2.0 moles. Even more preferably in the range of 0.2 to 1.15 mole percent. Good.   The fluoropolymer provides sufficient carbon-carbon unsaturation of the fluoropolymer to provide Deflation by any method that creates strong adhesion between the fluoropolymer and the substrate It may be hydrogenated. Preferably, the dehydrofluorination process is a fluoropolymer Does not introduce much grafting substituents. "A considerable amount" means, for example, dehydrofluorination About 2 mole percent relative to the number of comonomer containing the functionalized fluoropolymer Means more than g. Desirably contains dehydrofluorinated fluoropolymer Less than about 1 mole percent, based on the total number of copolymerized polymer units Less than about 0.5, preferably 0.2 or most preferably 0.1 mole percent Less adhesion promoting groups are introduced into the fluorinated polymer during dehydrofluorination. Removal In the case of hydride bulk fluoropolymers, a modest amount of graft substituent The incorporation into the fluoropolymer preferably involves the physical or mechanical properties of the fluoropolymer. Does not change gender in an identifiable manner.   Many suitable dehydrofluorination methods are well known in the fluoropolymer art. is there. For example, dehydrofluorination of bulk fluoropolymer Is dissolved in a solution of an organic solvent, even when carried out by a solvent-based method. Good. If necessary, add a basic reagent to the solution in the presence of a phase transfer catalyst to remove This produces hydrogen fluoride. Common solvents include tetrahydrofuran and methyl isobutyrate. Ketone, methyl ethyl ketone, acetone, n, n-dimethylformamide, di Methylacetamide and the like. For example, US Patent Nos. 3,507,844, 4,742,126 and 4,758,6 See No. 18. Alternatively, dehydrofluorination involves adding the fluoropolymer to an organic solvent And the solvent phase is dissolved in an aqueous phase containing an alkali metal hydroxide and a phase transfer catalyst. May be carried out by a two-phase solvent method. Useful catalysts are fluoropolymer technology Well known in the art, for example, tetrabutylammonium bromide (TBAB), Traalkylphosphonium halide, alkylarylphosphonium halide, Includes alkyl ammonium halides and alkyl phosphonium halides . See U.S. Patent No. 4,742,126. According to yet another alternative, " Dry bulk dehydrofluorination method referred to in the art as "reactive extrusion method" May be used to dehydrofluorinate the fluoropolymer. By these methods For example, by a dry basic process using an extruder or a ball mixer. Carry out hydrofluorination.   Compare also the dehydrofluorination of fluoropolymers in aqueous fluoropolymer emulsions Under basic mild conditions, in a basic aqueous medium substantially free of organic solvents , Preferably in a 100 percent aqueous medium containing no organic solvents. Can be carried out in the presence of a surfactant having a suitable emulsifying action according to the above. This According to the aqueous dehydrofluorination process of formula (I),Wherein X and X ′ are each independently either hydrogen or an electron withdrawing group Fluoropolymer emulsions containing fluoropolymers having structural fragments according to Can be added. Addition of basic compound to fluoropolymer emulsion As a result, the hydrogen atoms are acidic enough to dehydrofluorinate the fluoropolymer. You.   Examples of suitable basic compounds include ethylamine, potassium hydroxide (KOH), hydroxyl Ammonium chloride (NHFourOH), sodium hydroxide (NaOH), lithium hydroxide ( Hydroxides such as LiOH); potassium carbonate (KTwoCOThree), Sodium carbonate (NaTwo COThree) And the like.   An amount that does not interfere with the stability of the emulsion and thus does not cause aggregation of the fluoropolymer Is added to the emulsion. As used herein, "agglomeration" The term refers to the condition in which a fluoropolymer precipitates from an emulsion. Then basify Sufficient to react the compound with the -CFX-CHX 'reactive site of the fluoropolymer. Place the emulsion under the reaction conditions, thereby converting the fluoropolymer to hydrogen and fluorine atoms. Can form an unsaturated -CX = CX'- sequence in the fluoropolymer. Wear. The aqueous dehydrofluorination reaction conditions (ie, reaction time and temperature) Initiate a hydrogen sulfide reaction to produce specific fluoropolymers and selected basic compounds And depending on the desired degree of unsaturation of the resulting dehydrofluorinated fluoropolymer Any reaction time and any reaction temperature may be used. This water deflation In the hydrogenation process, the reaction temperature is relatively mild, for example in the range of about 40-100 ° C. It may be an enclosure. The reaction time can be any useful reaction time, but is preferably Or about 6 to 100 hours.   The surfactant having an emulsifying action in the fluoropolymer emulsion is a fluoropolymer. Various emulsifying surfactants well known in the emulsion art It may be one of the agents. These include, for example, anionic surfactants such as fatty acid soaps. Acid (stearic acid, lauric acid, sodium or potassium palmitate), sulfuric acid And sulfonates (sodium lauryl sulfate and dodecylbenzenesulfate) Sodium phonate), poly (ethylene oxide), poly (vinyl alcohol) and Containing hydroxyethylcellulose and perfluorinated carboxylic acids Nonionic surfactants such as surfactants are included. These and other emulsifying surfactants The surfactant may be used alone or in combination with two or more emulsifying surfactants. May be present in an effective amount, ie, an amount that produces an emulsion (eg, George   George Odian, Principles of Po lymerization, 3332-3 (2nd edition, 1981))   The dehydrofluorination method described above uses bulk fluoropolymers (eg, fluoropolymers). -Granules) or the dehydrofluorination of fluoropolymer emulsions. These ba Defluoridation of fluoropolymers during the dehydrofluorination process Hydrogenation is preferably used to produce a dehydrofluorinated fluoropolymer. About 0.01 mole percent to 20 mole percent based on the number of copolymerized monomer units. From about 0.02 mole percent to about 2.0 mole percent. Is particularly preferred.   Two embodiments using a dehydrofluorinated polymer include the following:   1. Cure of epoxy monomer in the presence of dehydrofluorinated polymer To provide a semi-IPN having some chemical bonds between the xy and fluoropolymer chains. Offer.   2. Dehydrofluorinated polymers and functionalities (ie acidification, eg Epoxy curing in the presence of blends with polyolefins Between the xy and fluoropolymer chains and between the epoxy and polyolefin chains. A semi-IPN having several chemical bonds is provided.   Epoxy resins useful in the present invention are preferably 1,2-, 1,3- and 1,4. 1,2-, 1,3- and 1,4-rings, which may be known as epoxides One or more ethers. Such compounds are saturated or unsaturated, aliphatic, May be aliphatic, aromatic or heterocyclic, or a combination thereof May be included. Contains one or more epoxy groups (ie, polyepoxides) Are preferred. Monoepoxy monomers useful in the present invention include 3-hydroxy 1,2-polyethylene oxide, oxacyclobutane, cyclohexane Oxide, indene oxide, styrene oxide, butyl glycidyl ether Phenyl glycidyl ether, cresyl glycidyl ether, n-butyl Enol glycidyl ether, vinylcyclohexane monooxide, octile Oxide, α-pinene oxide, limonene oxide and 3-pentade Includes silphenyl glycidyl ether.   Aromatic polyepoxides that can be used in the present invention (i.e., at least Compounds containing one aromatic ring structure, such as a benzene ring and two or more epoxides Bisoxyphenol A type resins and their derivatives, epoxy cresol Lunovolak resin, bisphenol-F resin and their derivatives and Polyglycidyl ether of polyhydric phenols such as poxyphenol-novolak resin And glycidyl esters of aromatic carboxylic acids, such as diglycidyl phthalate Jill ester, diglycidyl isophthalate, triglytrimellitic anhydride Sidyl ester and tetrapyrimellitic acid tetra Glycidyl esters and mixtures thereof are included. Preferred aromatic polyepoxy Koxide has been purchased by Shell Chemicals of Houston, Texas. electricals, Inc.), EPON 828 and EPON 1001F , Registered trademark EPON series of diglycidyl ether of bisphenol-A Is a polyglycidyl ether of a polyhydric phenol.   Representative aliphatic cyclic polyepoxides useful in the present invention (ie, cycloaliphatic compounds One or more saturated carbocycles and two or more epoxy group cyclizations, also known as Compounds containing cyclic compounds) include vinylcyclohexanedioxide (ERL) -4206), 3,4-epoxycyclohexylmethyl-3,4-epoxycycline Rohexanecarboxylate (ERL-4221), 3,4-epoxy-6-methyl Lecyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarbo Xylate (ERL-4201), bis (3,4-epoxy-6-methylcyclo Xylmethyl) adipate (ERL-4289), dipentenedoxide (ER L-4269) and 2- (3,4-epoxycyclohexyl-5,1 "-spin B-3 ", 4" -epoxycyclohexane-1,3-dioxane, 4- (1,2 -Epoxyethyl) -1,2-epoxycyclohexane and 2,2-bis (3 , 4-epoxycyclohexyl) propane and the like in Danbury, Connecticut Alicyclic Epo manufactured by Union Carbide Corp. Includes the series "ERL" of oxide. Preferred alicyclic polyepoxy Is a registered trademark ERL series.   Representative aliphatic polyepoxides (ie, containing no carbocycle and having two or more 1,4-bis (2,3-epoxypropoxy) ) Butane, glycerol, polypropylene Polyglycidyl of aliphatic polyol such as glycol, 1,4-butanediol, etc. And diglycidyl esters of dimers of linoleic acid and linoleic acid.   A wide variety of commercially available epoxy resins are available, such as Lee and The Handbook of Epoxy Resins by Neville (the Hand) book of Epoxy Resins), McGraw-Hill (McGraw-H) ill book Co.), New York (1967), epoxy resin, chemistry and technology. Surgery (Epoxy Resins, Chemistry and Technology) y), 2nd edition, edited by C. Mary, Marcel Decker (Marcell)  Decker, Inc.), New York (1988) and epoxy resin technology ( Epoxy Resin Technology), Bruins (PFBr) uins), Interscience Publ isers), New York (1968). So Any of the epoxy resins described herein may be used in making the semi-IPN of the present invention. Can be useful.   Optionally, monohydroxy- and polyhydroxy-alcohols are It may be added to the curable composition of the present invention as a xy resin chain extender. Suitable Examples of suitable alcohols include methanol, ethanol, 1-propanol, and 2-propanol. Panol, 1-butanol, 1-pentanol, 1-hexanol, 1-hepta Nol, 1-octanol, pentaerythritol, 1,2-propanediol , Ethylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,4-cyclohexane Including, but not limited to, chlorohexanediol and glycerol. Preferably, it contains a hydroxyl group Compounds, especially compounds containing about 2 to 50 hydroxyl groups, resulting in a weight average molecular weight Compounds having about 50-25,000, preferably about 50-2000, such as Ester, polyether, polythioether, polyacetal, polycarbonate , Poly (meth) acrylate, and at least 2, generally about 2-8 But preferably polyesteramides containing about 2 to 4 hydroxyl groups, or The prepolymers containing hydroxyl groups of these compounds are also representative useful compounds according to the present invention. For example, a higher polymer (High) by Saunders. Polymers), Volume XVI, "Polyurethanes, Chemistry and Technology (Polyuret) hanes, Chemistry and Technology), I, 32 -42 pages, 44-54 pages and Volume II, 5-6 pages, 198-99 pages (1962, 1964) and the Kunstoff Handbook (Kuns tsoff-Handbuch), Volume VII, pp. 45-71 (1966) )It is described in. Of course, it contains at least two hydroxyl groups and has a molecular weight of about 50 to 50,000 mixtures of the above compounds, such as polyethers and polyesters It is acceptable to use a mixture with   Contains at least two reactive hydroxyl groups suitable for use according to the invention Low molecular weight compound (molecular weight of about 50 to 400) preferably contains a hydroxyl group, Generally, compounds containing about 2 to 8, preferably about 2 to 4 reactive hydroxyl groups. is there. It also contains at least two hydroxyl groups and has a molecular weight of about 50 to 400. It is possible to use mixtures of different compounds. Examples of such compounds are , Ethylene glycol, 1,2- and 1,3-propylene glycol, 1,4 -And 2,3-butylene glycol, 1,5-pentanediol, 1,6- Xandiol, 1,8-octanediol , Neopentyl glycol, 1,4-cyclohexanedimethanol, 1,4- Cyclohexanediol, trimethylolpropane, 1,4-bis-hydroxy Methylcyclohexane, 2-methyl-1,3-propanediol, dibromobuta Diol (US Pat. No. 3,723,392), glycerol, trimethylol Propane, 1,2,6-hexanetriol, trimethylolethane, pentae Risuritol, quinitol, mannitol, sorbitol, diethylene glycol , Triethylene glycol, tetraethylene glycol, high-grade polyethylene glycol Recall, dipropylene glycol, high-grade polypropylene glycol, dibutyle Glycol, higher polybutylene glycol, 4,4'-dihydroxydiphenyl Lupropane and dihydroxymethylhydroquinone.   Other polyols suitable for the purposes of the present invention are hydroxy aldehydes and hydrides. Mixes with roxyketone ("formose") or with metal compounds as catalysts Form in the presence of a compound capable of forming enediol as a medium Polyhydric alcohol obtained by reduction formed during self-condensation of aldehyde hydrate Cole ("formitol") (e.g., German Offenlegun) gsschrift No. 2,639,084, No. 2,714,084, No. No. 2,714,104, No. 2,721,186, No. 2,738,154 And No. 2,738,512).   Carbowax, poly (ethylene glycol), poly (ethylene glycol methyl Ether), poly (ethylene glycol), tetrahydrofurfuryl ether, Polyfunctional alcohols such as poly (propylene glycol) may also be used in the compositions of the present invention. It is considered that it can be used.   The mixture of THV and epoxy within the present invention is a combination that allows for the production of semi-IPN. A miscible window having a compositional range can be defined. Epoxy monomer At the time of the addition, no drop in the crystal starting point of THV200 was observed. Melting point drop The drop in crystal point observed with is indicative of thermodynamic partial miscibility. Partial mixing is narrow Only over a range of conditions is the composition / temperature / pressure observed homogeneous It was a solution. Scanning differential measurement measured between room temperature and 200 ° C As shown by, the region of heat generation due to crystallization and heat absorption due to melting are THV / ep It decreased as the epoxy content of the xy-semi-IPN increased. This is relatively low The crystal content of the less expensive (<20%) fluoropolymer is due to the presence of the epoxy monomer. Revealed that he was adversely affected. Most epoxy monomers are THV (Swollen) amorphous components.   The catalyst for curing the epoxy of the present invention may be a thermal or photochemical means. Can be activated by either of Preferred catalysts are heat activated.   There are two general types of well-known photocatalysts: onium salts and cationic Metal salts, both of which are useful in the present invention.   Onium salt photoinitiators for cationic polymerization include iodonium and sulfonium Um complex salts. Useful aromatic iodonium complex salts have the general formula: (Where   Ar1And ArTwoAre the same or different and are aromatic groups having 4 to about 20 carbon atoms And selected from the group consisting of phenyl, thienyl, furanyl and pyrazolyl groups. Re;   Z is oxygen, sulfur, a carbon-carbon bond, Wherein R is an aryl group (of 6 to about 20 carbon atoms such as phenyl) or An acyl group having 2 to about 20 carbon atoms, such as cetyl or benzoyl), And(Where R1And RTwoIs hydrogen, an alkyl group having 1 to about 4 carbon atoms and a carbon atom Selected from the group consisting of alkenyl groups having 2 to about 4 children). Re;   m is 0 or 1; and   X is the formula DQn(Where D is the Ith of the Periodic Table of the Elements (Chemical Abstract Version) A metal of Group B to Group VIII or a metalloid of Group IIIA to Group VA; Q is a halogen atom, and n is an integer of 1 to 6). Preferably, the metal is copper, Zinc, titanium, vanadium Chromium, magnesium, manganese, iron, cobalt, or nickel; Metalloids are preferably boron, aluminum, antimony, tin, arsenic and This is Rin. Preferably, halogen, Q is chlorine or fluorine. Suitable ani Example of ON is BFFour -, PF6 -, SbF6 -, FeClFour -, SnClFive -, AsF6 -, SbFFiveOH-, SbCl6 -, S bFFive -2, AlFFive -2, GaClFour -, InFFour -, TiF6 -2, ZrF6 -, CFThreeSOThree -, N (SOTwoCFThree)Two -, And And C (SOTwoCFThree)Three -It is. Preferably, the anion is BFFour -, PF6 -, SbF6 -, AsF6 -, S bFFiveOH-And SbCl6 -It is. More preferably, the anion is SbF6 -, AsF6 -And And SbFFiveOH-It is.   Ar1And ArTwoThe aromatic group can optionally have one or more fused benzo rings (eg, Naphthyl, benzothienyl, dibenzothienyl, bonzofuranyl, dibenzofuran And the like. Desirably, the aromatic group is one or more non-basic groups. If it does not essentially react with the pentoxide and hydroxyl functional groups, You may.   Useful aromatic iodonium complex salts are described in U.S. Pat. It is described in more detail in US Pat. No. 4,256,828. Preferred aromatic iodoni Um complex salt is (Ar)TwoI PF6And (Ar)TwoI SbF6It is.   Aromatic iodonium complexes useful herein are sensitive only in the ultraviolet spectral region Sex. However, they are well known for photodegradable organohalogen compounds. May be sensitized in the near ultraviolet and visible spectral ranges. Increase Examples of sensitizers include US Patent No. 4,250,0, which is incorporated herein by reference. No. 53, including aromatic amines and colored aromatic polycyclic hydrocarbons. I will.   Suitable aromatic sulfonium complex salt initiators for use herein are the following general The expression is: (Where RThree, RFourAnd RFiveMay be the same or different, provided that At least one of the groups is aromatic. These groups contain from 4 to about 4 carbon atoms. 20 aromatic groups such as substituted and unsubstituted phenyl, thienyl and furanyl ) And an alkyl group having 1 to about 20 carbon atoms. The term “alkyl” includes substituted alkyl groups (eg, halogen, alkoxy And substituents such as aryl). Preferably, RThree, RFourAnd RFiveIs Each being aromatic;   Z, m and X are all as defined above for the iodonium complex salt ).   RThree, RFourAnd RFiveIf is an aromatic group, optionally one or more fusions Benzo ring (eg, naphthyl, benzothienyl, dibenzothienyl, benzofura Benzyl, dibenzofuranyl, etc.). If desired, the aromatic group can be When one or more non-basic groups do not essentially react with the epoxide and hydroxyl functions May be replaced by them.   Triphenylsulfonium hexafluoroantimonate and p- (phenylene) (Thiophenyl) diphenylsulfonium hexafluoroantimonate Are preferred sulfonium salts. Useful sulfonium salts Is described in more detail in U.S. Pat. No. 5,256,828.   Aromatic sulfonium complexes useful in the present invention are light sensitive only in the ultraviolet spectral region It is. However, U.S. Patent Nos. 4,256,828 and 4,250, By a selective group of sensitizers, such as those described in US Pat. And in the visible spectral range.   Suitable photoactivatable organometallic complexes useful in the present invention are incorporated herein by reference. US Patent Nos. 5,059,701, 5,191,101 and And No. 5,252,694. Organometallic cation Such a salt of has the general formula:                            [(L1) (LTwo) Mm]+ eX- (Where   MmAre groups IVB, VB, VIB, VIIB and VIB of the periodic table Represents a metal atom selected from Group VIII elements, and is preferably Cr, Mo, W, Mn, Re and Co;   L1Are substituted and unsubstituted acyclic and cyclic unsaturated compounds and groups, and substituted Selected from the group consisting of and unsubstituted carbocyclic aromatic and heteroaromatic compounds May be the same or different ligands, each of which is a valence shell of a metal atom M 0, 1 or 2 ligands that can contribute 2 to 12 π-electrons Show. Preferably, L1Is substituted and unsubstituted ηThree-Allyl, ηFive-Cyclopentadi Enil, η7-Cycloheptatrienyl compound and η6-Benzene and substitution η6 A η selected from the group consisting of benzene compounds (eg, xylene)6-Compounds Having 2 to 4 fused rings Compound, each MmCan contribute 3 to 8 π-electrons to the valence shell of Selected from the group   LTwoMeans carbon monoxide, nitrosonium, triphenylphosphine, triphenyl The same or different Riga selected from the group consisting of rustybin and phosphorus derivatives Contributes to an even number of π-electrons, which may be1And LTwoIs MmContribute to 0 to 1 to 3 ligands whose total valence is the total remaining positive charge of the complex;   e is an integer of 1 or 2 and is the residual charge of the complex cation;   X is a halogen-containing complex anion as described above).   Examples of suitable salts of organometallic complex cations useful as photoactivatable catalysts of the invention To:       (η6-Bensen e) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -       (η6-Toluene) (ηFive-Cyclopentadienyl) Fe+1 AsF6 -       (η6-o, p, or m-xylene) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -       (η6-Cumene) (ηFive-Cyclopentadienyl) Fe+1PF6 -       (η6-Xylene (mixed isomer)) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -       (η6-Xylene (mixed isomer)) (ηFive-Cyclopentadienyl) Fe+1 PF6 -       (η6-o-xylene) (ηFive-Cyclopentadienyl) Fe+1 CFThreeSOThree -       (η6-m-xylene) (ηFive-Cyclopentadienyl) Fe+1 BFFour -       (η6-Mesitylene) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -       (η6-Hexamethylbenzene) (ηFive-Cyclopentadienyl) Fe+1 SbFFiveOH-You And       (η6-Fluorene) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -.   Is included. Preferred salts of organometallic complex cations useful in the present invention include the following 1 Contains more than one: (η6-Xylene (mixed isomer)) (ηFive-s cyclopentadienyl) F e+1 SbF6 -, (Η6-Xylene (mixed isomer)) (ηFive-Cyclopentadienyl) Fe+1 PF6 - , (Η6-o, p, or m-xylene) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -, And And (η6-Mesitylene) (ηFive-Cyclopentadienyl) Fe+1 SbF6 -.   If necessary, tertiary alcohol oxalate, etc. May be used in combination. U.S. Patent No. 5 which is incorporated herein by reference. The accelerator is preferably a total polymerizable mixture as described in U.S. Pat. To 10% by weight of the product (thermoplastic component, thermosetting component and catalyst) , Preferably 0.1 to 4% by weight.   Useful commercial initiators include FX-512, an aromatic sulfonium complex (Minnesota) 3M Company, St. Paul, U.S.A., registered trademark UVI-6974, Aromatic sulfonium complex (Union Carbide, Danbury, CT) Union Carbide Corp.) and registered trademark IRGACURE26 1. Cationic organometallic complex (Ciba-Geigy Chemical, Hawthorne, NY) (Ciba Geigy Chemicals).   Photoinitiators useful in the present invention are from 0.01 to 10 based on the total curable resin composition. Weight percent, preferably 0.1 to 5 and most preferably 0.1 to 2 weight percent. May be present in an amount in the range of 0.1-0.1%.   Certain heat-activated curing agents for epoxy resins (eg, added to chemical reactions) Compounds which affect the curing and crosslinking of epoxides) And useful. Preferably, such a curing agent is present at the temperature at which the components are mixed. And thermally stable.   Suitable thermosetting agents include aliphatic and aromatic primary and secondary amines. Min, for example di (4-aminophenyl) sulfone, di (4-aminophenyl) Ether and 2,2-bis- (4-aminophenylpropane; aliphatic and aromatic Aromatic tertiary amines such as dimethylaminopropylamine and pyridine; quaternary Ammonium salts, especially N-methyl-4-picolinium hexafluorophosphate Pyridinium salts such as Fluorenediamines such as those described in 684,678; BFThree・ EtTwoO and BFThree・ HTwoNCTwoHFiveBoron trifluoride complex such as OH; methyl imidazo Imidazoles such as hydrazine: hydrazines such as adiphydrazine; and tetramethyi Luguanidine and dicyandiamide (cyanogua, commonly known as DiCy) Guanidine). Many of them are high melting polyolefins The use of these components may be inappropriate if any Care should be taken when choosing a low melting point polyolefin and epoxy resin. They can be useful in producing semi-IPNs of the invention containing It should be understood.   High temperature epoxy catalysts are particularly useful in the present invention. Simple pyridinium, quinolini , Iodoreninium, benzothiazolium, alkyl, aryl and al Killaryl ammonium and phosphonium salts in the range of 250-350 ° C And has been found to be an effective initiator for cationic polymerization of epoxies. This Due to their high exothermic temperatures, these catalysts are, for example, Particularly suitable for use at high extrusion temperatures of 200 ° C. and above. This composition is pressed Crosslinking during this processing step is stable in the dispenser, i.e. they do not cure The problems that may arise due to are eliminated. When finally cured, these The composition provides surprisingly strong lamination shear bond strength.   Generally, salts centered on cationic nitrogen are active in this temperature range . The surprising result is that these changes when changing the anion and keeping the cation constant This is the order of the exothermic temperatures of the compound series. Exothermic temperature PF6 -<AsF6 -<SbF6 -Increase in order I do. Those skilled in the epoxy resin art would expect the order to be the opposite. This is surprising in that it is done.   Classes of salts useful as thermosetting agents include pyridinium, quinolinium, and benzoquinone. Sazolium, benzothiazolium, indolenium, ammonium, and phos Honium salts. Particularly suitable as a catalyst for epoxy / polypropylene compositions The structures of the salts found to be include: Wherein R is an alkyl group or an aryl group, and R ′ is an alkyl group or an acyl group. R ″ is an alkyl group or an aryl group. Or R ′ ″ is an alkyl group or an aryl group). R and R 'may form a cyclic structure having 4 to 8 carbon atoms. (R, R 'and R' '' May form a bicyclic ring structure. ) The alkyl group has 1 to 12 carbon atoms. The aryl group may be a fused ring of 1-3 (e.g., naphthalene) or carbon atoms. Up to 30 bound odors (eg, biphenyl) may be present. Each cationic charge is suitable An appropriate number of anions, X-Should be balanced by   Also, here X-May be as defined above, preferably X-Is BFFour - , PF6 -, AsF6 -, SbF6 -Or CFThreeSOThree -And most preferably X- Is PF6 -It is.   Here, each R, R ', R ", R" "is independently alkyl having up to 20 carbon atoms. , An aryl or alkaryl group, wherein X is as defined above. You.   The thermosetting agent has a ratio of epoxy equivalent to thermal epoxy curing agent equivalent of 0.9: 1 to 1: 1. It may be present in an amount such that it is in the 2: 1 range.   The thermosetting may be performed before or after the thermoplastic has crystallized. Ho In most possible applications, the film is ready to be manufactured into a final product. There is no need to cure the film with. Thermoplasticizer molecular orientation needs to be preserved In some cases, in-line curing may be desirable.   Various adjuvants may be added to the composition of the present invention to alter the physical properties of the semi-IPN after curing. It can also be added to objects. Useful adjuvants include thixotropes such as fumed silica. Loppy agent; color enhancement face such as ferric oxide, carbon black and titanium dioxide Materials such as mica, silica, calcium carbonate, magnesium sulfate and calcium sulfate Any filler; clay such as bentonite; glass beads and bubbles; Stell, polyimide, glass fiber, poly (p-phenylene) Polyamides such as terephthalamide) and carbon fibers and ceramic fibers. Machines and reinforcement materials such as unidirectional webs of inorganic fibers and nonwoven webs are included. 10 Up to about 200 parts adjuvant is used per 0 parts polyolefin-epoxy composition. May be.   In addition to the above additives and auxiliaries, fluoropolymer resins and epoxy resins Adding one or both of polyolefins and polyamides to the mixture of Are within the scope of the present invention.   "Polyolefin" as used herein is preferably a cationic, anionic On or Ziegler-Natta-type polymerization process From homopolymerization and / or copolymerization of hydrocarbon olefin monomers , Fully pre-loaded polymeric hydrocarbons essentially free of organic functional groups Say. Homopolymer polyolefins useful herein include polyethylene, polyethylene Propylene, poly-1-butene, poly-1-pentene, poly-1-hexene, Li-1-octene and related polyolefins are included. Preferred homopoly Merpolyolefins include polyethylene (eg, Dow25455, Dow Chemical Co., Midland, Michigan )) And polypropylene (eg, Shell DS5D45, Shell Chemicals, Houston, TX , Inc.) or registered trademarks Exxon 3445 and registered trademark 3505, Exxon Chemicals, Houston, TX )) Is included. Poly (ethylene-co-propylene) (for example, registered trademark SR D7-462, registered trademark SRD-463 and registered trademark DS7C50, Manufactured by Shell Chemicals, Inc.), Poly (Pro Pyrene-co-1-butene) (for example, registered trademark SRD6) -328, manufactured by Shell Chemicals, Inc. ) And related copolymers. It is for. A preferred copolymer is poly (ethylene-copolyethylene). Huls Ame, Piscataway, NJ Rica Inc.) registered trademark Vestoplast series Is also useful.   The polyolefin useful in the present invention is a fluoropolymer for polyolefin. Is from 1:99 to 99: 1, preferably from 25:75 to 75:25, most preferably May be present in an amount such that it is in the range of 50:50. Polyolefin and full When a mixture with the oropolymer is present, the epoxy resin component is preferably For all ratios of polyolefin: fluoropolymer, about 1 of the total weight of the mixture 0 to about 15% by weight.   As used herein, "polyamide" refers to an amide group in the polymer skeleton,- A fully prepolymerized condensation polymer characterized by the presence of CONH- U. Polyamides can be used in many applications such as dicarboxylic acids or dicarboxylic acid halides. By condensation polymerization of a functional carboxyl-containing species with a polyfunctional amine, or By the self-condensation of a bifunctional molecule having both Manufactured. Reactive species are independently aliphatic, aromatic, carbocyclic, polycyclic, saturated, unsaturated It may be a sum, straight chain or branched chain. Polyamide has one polycarboxyl function Even if it is a polymerization product of a sex species and one polyamine species, And a mixture of polyamine species and a mixture of polyamine species. The industry has many A polyamide route has been developed, all of which are intended to be included within the provisions of the present invention. Illustrated. A broad class of polyamides known as "nylons" Is the most abundant in the market, but the provisions of the present invention are intended to be limited thereto I haven't. Preferred polyamides for the present invention include Wilmi, Delaware. Nylon6 and Nylon66 manufactured by DuPont Co. , Nylon12 and Nylon group of materials and Ambler, PA Of the Versamide family of products from Henkel Corp. Polyamides are included.   Polyamides useful in the present invention have a fluoropolymer to polyamide ratio of 1 : 99-99: 1, preferably 25: 75-75: 25, most preferably 50: It may be present in an amount such that it is in the range of 50. Polyamide and fluoropolymer When a mixture with is present, the epoxy resin component is preferably a polyamide: For all ratios of fluoropolymer, from about 10 to about 15 parts by weight of the total weight of the mixture Includes   Fluoropolymer-epoxy semi-IPN is protective coating, adhesive, self-supporting fill It is useful in multilayer assemblies as a system. Most preferably, the semi-IPN of the present invention As a structural adhesive for metals, plastics, glass or ceramics; Useful as a self-supporting hot melt adhesive; or as a protective coating. Preferred In a preferred embodiment, the fluoropolymer-epoxy semi-IPN is coated on a flexible substrate. It can be overturned to produce an adhesive tape. For special applications, semi-IPN Multilayer collection for electrical and communication cables with cover and film Can be present in the product. In another preferred embodiment, the fluoropoly Mer-epoxy semi-IPN for storage or transportation of hydrocarbon fuels such as gasoline The polymer used, preferably a polyolefin, more preferably a polypropylene Pyrene tanks or containers can be coated with the semi-IP of the present invention. N is a polyolefin container and the resulting fluoropolymer (eg, poly ( Acts as a binder between tetrafluoroethylene) (PTFE)) protective coating It can be an intermediate (or "bonded") coating. The semi-IPN of the present invention also provides Metal tanks used for transport and storage of materials or direct An immediate application is found.   The objects and advantages of the present invention are further illustrated by the following examples, which Specific materials and their amounts, as well as other conditions and details, referred to in the It should not be construed to inadvertently limit the light. Example Procedure of test Tensile coefficient, tensile strength   5KN load cell, model number 2511-317 equipped with Instron (Inst ron) Tensile tester (Instron Corp., Illinois) Tensile modulus and tensile strength were measured using Parkridge, Illinois. Black Shead speed and gauge length were varied for each test as indicated. Laminated shear; peak load   Laminate shear measurements are essentially ASTM D1002-94, "Single- Apparent shear strength (Ap parent Shear Strength of Single-Lap-Jo int Adhesively Bonded Metal Specimens by Tension Loading) ". 11.43 cm × 2. 54cm × 3.2mm cold rolled steel copper coupons were extracted with methyl ethyl keto Washed thoroughly and heated to about 185 to about 250 ° C. on a hot plate. A film having a thickness of about 0.25 and 0.75 is applied to a silicone rubber roller. Used to apply to hot metal surface and melt. Melt film containing photocatalyst While TLD15W / 03 (Phillips, The Netherlands) Or 350BL (Siemens Corp.) / Osramsil Osram Sylvania Inc., Dunn, Mass. Birds) 3.1 J / cm with UV-emission lampTwoExposed to the radiant energy of Was. The two cured halves are used as Scotchkote 134 Epoxy (registered trademark) Film side by 3M Company, St. Paul, Minn. They were glued together. Stacking area is 2.54cmTwoMet. At 185 ° C, very Put a thin registered trademark Scotchkote on one half and the other half on it I put it. A piece of film to be tested is placed between the two coupons at 225 ° C for 5 minutes. A sample containing the thermosetting system was produced by placing. Then add to the sample The heating was stopped and the temperature was cooled to 22 ° C. B equipped with a 44.5KN load cell Peak load and breaking strain were recorded on an Instron apparatus. Dielectric constant   Essentially, Keithly 237 and 8008 resistive locking and ASTM D2 using a charge time of 60 seconds at 500 volts and 45% relative humidity. The measured value of the dielectric constant was measured according to 57-93. HP16451B dielectric constant test fixed Apparatus (Dielectric Test Fixture) (Park, CA) Roalto Equipped with Hewlett-Packard Co. HP4284A Precision (Precision) LCR meter The measured value at 500 mHz was measured. HP16451A dielectric constant test fixture (D HP4291 using the Electric Test Fixture.AI Impedance / Material Analyzer lAnalyzer) was used to measure the measured value at 900 mHz. Example 1   The composition can be manufactured in at least two ways. In method A, dry The dehydrofluorinated THV200 powder was added to the total weight of the thermoplastic polymer components. Sigma blade with 2 to 10 weight percent registered trademark PR500 Equipped with pre-heated Brabender internal mixer Mix at 185 ° C. in a sir. The sample was then melt pressed to the desired thickness. Details of the dehydrofluorination are described in U.S. Pat. Nos. 3,507,844 and 4,758,6. No. 18 and U.S. Patent Application Ser. No. 08 / 703,422. .   In method B, a film was produced using a twin screw extruder. Register Trademark PR500 (containing a mixture of epoxy and fluorenamine curing agent) , Were added by a side port downflow of the fluoropolymer pellet feed port. Haake with static mixer and 15.2cm (6 ") sheet die (Haake) Counter-Rotating Conical Twin Screw Extruder (31.8 / 2) The sample was extruded at 0 rpm (rear / front) at a screw speed of 90 rpm. Offering 86-9 temperature profile from feed to die 2-92-86. The take-up wheel was maintained at 25 ° C. Line speed The degree is 30.5 cm / min (1 ft / min) and the thickness of the extrudate is 381 micrometers -(15 mil). Dielectric and adhesive properties   In semi-IPN, the physical state of the thermoplastic during curing of the thermosetting agent has special curing characteristics. Important to develop.   Lamination or bonding on metal is performed using UV or heat curing. Bonding To do so, the substrate is heated above the melting point of the thermoplastic and then irradiated. Is required. The minimum cycle of the thermosetting system is 5 minutes at 225 ° C. Was. If placed on the sample for 5 minutes at 2.54 cm (1 "), Sylvan ia350BL valve (Siemens Corp.) / OSRAM Osram Sylvania Inc., Mass. Danvers) may be used. Preferred glass transition temperature after exposure at room temperature Is then oven cured at elevated temperatures to increase to over 150 ° C in the thermoset phase is necessary. Radiation dose is 2-3 J / cmTwoUse a melting lamp for as long as May be used. The sample was then removed from the heat source and cooled to room temperature. Laminated shear The test was used to determine the adhesion at room temperature. The data in Table 1 shows the hardness of the thermosetting agent. 4 shows the adhesive properties obtained when the thermoplasticizer was melted during the formation.   The data in Table 1 shows the increase in modulus seen with the different compositions. Tension posted The property is that it cures with a melting lamp at room temperature, i.e. the thermoplastic is solid It is obtained by curing when it is in a state. Curing of thermosetting agent If the thermoplastic did not melt at this time, low adhesion occurred. Increase in tensile modulus Was observed when curing occurred after the thermoplastic crystallized.   For both UV curing and thermal curing, similar products can be obtained without dehydrofluorination. The layer shear strength values are shown. Dehydrofluorination is up to about 11.6MPa Increased the degree. Similar values of adhesion are given by THV / stereore (gullar) -polyolefin / epoxy system. Dehydrofluorination THV / epoxy semi-IPN samples, including those that did not adhere. THV / Polyolefin epoxy and polyolefin / epoxy semi-IPN are sticky Did not.   Stereoregular poly in THV / epoxy system The addition of the olefin also increased the tensile strength. This is exactly the phase-separated microstructure It is considered to be. Nobunaka as a result of hard additives in a soft matrix Sex decreased. THV / polyolefin / epoxy extrudate has very good appearance Extrusion was easy. DS7C50 is polypropylene with 20% rubber phase content there were. The rubber phase is a fully saturated ethylene (55%) propylene copolymer ( 45%). For polypropylene homopolymer The resulting rubber had a molecular weight ratio of 1: 5. The rubber content in polypropylene is The optimum connection for THV / polyolefin / epoxy semi-IPN Wear characteristics are provided. Example 2   THV semi-IPN coatings and films are used for electrical cables and communiqués In a multi-layer assembly of the cable.   In electrical assemblies, properties such as dielectric strength, dielectric constant and dielectric loss It can be used to measure the utility of the semi-IPN of the invention. Described earlier The results of these measurements on the cured THV200 / epoxy semi-IPN It is shown in Table 2.  The data in Table 2 shows that less than 10 weight percent polyolefin (DS7C50) Or mixed with maleated polyolefin (registered trademark Epolene G3003) Matching does not affect the dielectric constant or loss 2 shows that the dielectric strength of increases significantly. A relatively high amount of 50 weight percent D When adding S7C50 polyolefin, the dielectric strength is further increased significantly. However, both the dielectric constant and the dielectric loss were significantly reduced. For comparison, ASTM D Shortest period of unoriented plastic evaluated using 149-94 The dielectric strength between them is 1.5 kV / 25.4 micrometer for cross-linked polyvinyl chloride. Was observed. Relatively small amount of cationically cured aromatic epoxy (sample By adding 2B), the dielectric strength of THV200 is not affected. It is noted that both the dielectric constant and the dielectric loss have been significantly reduced. Example 3   The epoxy-fluoropolymer semi-IPN of the present invention was prepared by an extrusion process. Fluoropolymer, epoxy resin and catalyst are introduced into monomer extruder 0.16 mL / turn of Zenith HP In a Haake conical twin screw extruder equipped with a B gear pump Mixed. The temperature curing point in the extruder is 271 ° C, all are cured and the actual The wash temperature was generally 234-273-271-271 ° C. Prepare 6 samples Was:   In Table 3 above, FEP-100 is a DuPont in Wilmington, Del. Poly (tetrafluoroethylene-co-hexa) manufactured by DuPont Co. EP-610 is from Daikin of Japan. Poly (ethylene-cotetrafluoroethylene); Kynar 74 0 is Elf Atoc, Philadelphia, PA. Hem) poly (vinylidene fluoride), MP was prepared as in Example 6. ) N-methyl-4-picolinium hexafluorophosphate.   An extrudate (10.16 cm × 2.54 cm) was placed on the substrate, and the composition was By heating at a temperature of up to 71 ° C for 5 minutes, a sample of about 380 micrometers can be obtained. Material is based on steel, polyamide film and Teflon film. It was quantitatively tested for the adhesiveness to the material. Samples 3D and 3F were made with steel Demonstrated marginal adhesion, but none for polyamide or Teflon won. Samples 3A, 3B, 3C and 3E can be applied to any substrate under these conditions. Again, no adhesion was shown.   Similarly, a second set of samples was applied to each of the substrates and at 271 ° C. for 15 minutes. For a while. Again, samples 3D and 3F showed adhesion to steel. . Sample 3B exhibited slightly greater adhesion to Teflon than steel. However, all other samples did not show adhesion to Teflon. Sample 3S And 3F showed weak crown adhesion to the polyamide film.   The adhesion of Sample 3D to steel copper is further shown below. 15x2.54x 5 strips of 0.03 cm 3D were placed on a 11.4 x 2.54 x 0.03 cm slide. Placed on a steel bar and heated at 299 ° C. for 15 minutes. During cooling, Place a bar of teal copper in one clamp of the Instron device And place the excess sample film in the other clamp and perform a 180 ° peel test. The peel value was obtained by the measurement. Using a gauge length of 7.62 cm, The head speed was 5.08 cm / min. The data is shown in Table 3b below.  As shown in Table 4, the tensile properties of Samples 3A to 3F were obtained. Receive directly from the extruder The "uncured" state and the sample Each composition was examined in a "cured" state by heating for minutes. Report in Table 4 Values were obtained at ambient temperature (about 23 ° C); gauge length was 2.54 cm and crosshead The speed was 5.08 cm / min. Values are for 5 samples per recorded data Report.   The data in Table 4 show that the tensile properties of the fluoropolymers Indicates that it is not adversely affected by mixing. Example 4   THV200 and 3.4% by weight of ERL-4221 epoxy resin (Shelke Shell Chemicals, Inc., Houston, Texas ) Containing a semi-IPN composition having a temperature profile of 192-222-22. The pellets were prepared at 1-219 ° C in an extruder with a feed rate of 14.2 g / min. Cap The strike wheel was maintained at 20 ° C; the line speed setting was 25. Triaryl Sulfonium hexafluorophosphate (FX-512 activated epoxy curing agent 3M Company, St. Paul, Minn. The catalyst concentration is single. %.   The resulting 10.2 cm × 2.54 cm × 0.0254 cm extrusion One part of the film is peeled off with two pieces of poly (ethylene terephthalate) (PET) Inner (Scotchpar polyester film, 3M Co., Ltd.) mpany), St. Paul, Minn.). Second part of the same dimensions The fractions are pre-UV coated as described in US Pat. No. 4,822,451, Example 5. It was placed between two pieces of PET release liner that had been treated with radiation. Two samples Was placed on a hot plate at 190 ° C., and was A (Sylvania) 350 Blacklight (Blacklight) UV Raw valve (Siemens Corp.) / OSRAM Sylvania (Osram Sylvania Inc., Danvers, MA) Irradiation. Cool the irradiated sample and cut it into a 1.27 cm x 10.2 cm strip And then a crosshead speed of 1.27 cm / min and a gauge length of 2.54 cm. Using an Instron tensile tester (Model 1122) The adhesion to the inner was tested.   Minimum load of untreated PET liner: 0.0092 MPa   Minimum load of UV treated PET liner: 0.0070MPa Data show that the epoxy-fluoropolymers of the present invention are commonly used in the industry This shows that even a liner can exhibit moderate adhesiveness. Example 5   The present invention comprises a blend of a THV500 fluoropolymer and a corresponding polymer The light semi-IPN was prepared in a twin-screw extruder as described above. Combination The composition of the product is shown in Table 5. Examples 5A-5E were prepared for a 1 cm distance while contacting the following polymer films: Under UV irradiation for 5 minutes (Sylvania black light bulb) Heated at 185 ° C. on a hot plate covered with Teflon at:   1. PET release liner (registered trademark Scotchpar polyester film) )   2. Registered trademark polyolefin 1150-1 (Eastman Chemicals (Eas tman Chemicals, Kingsport, TN)   3. Registered trademark Elvamide 8064 nylon film (Dupont Chemical (DuPont Chemical Co., Wilmington, DE)   4. Registered trademark Tenite 1550P polyethylene (Eastman Chemicals 5% registered trademark Epolen in Eastman Chemicals Co. e (C18) Eastman Chemicals   5. Exact 4038 polyolefin, metallocene catalyst (Exxon)   Exxon Chemical Company, Hex, Texas Newton)   6.25% registered trademark ERL-4221 epoxy resin (Union Carbide ( Exxon 344 trademark mixed with Union Carbide Corp.)) 5 Propylene homopolymer (Exxon Chemical Co., Ltd.)  Company))   Adhesion of the epoxy-polymer blended semi-IPN of this example to six films The qualities were qualitatively observed as follows:   Examples 5A-5E are for PET (film 1) and nylon (film 3). The adhesive showed:   Example 5B is also a wax-added polyethylene (registered trademark Tenite 1550P). (Film 4) and metallocene polyolefin (film 5) Indicated;   Example C is also polyolefin 1150-1 (film 2), metallocene polyolefin. (Film 5) and polypropylene-epoxy (film 6) Showed good adhesion.   The data of Example 5 shows that nylon or functional polyolefin and THV of the invention Formulation after curing with epoxy semi-IPN has good adhesion to many polymer substrates Is shown. This formulation is applied to a polymer substrate such as polyethylene Useful as a tie layer in multi-layer polymer structures to facilitate the adhesion of the cladding obtain. Example 6   N-methyl-4-picolinium hexafluorophosphate catalyst (catalyst MP) Was prepared as follows:   50 g of 4-picoline (Aldrich Chem) ical Co.) and 76.2 g of indomethane (Aldrich Chemical Co. (Al 600 mL 1,2-dichloromethane with Drich Chemical Co.) The solution was stirred at room temperature of about 23 ° C. After a slight exotherm of the reaction, a precipitate forms, The mixture was stirred for about 3 hours and cooled to room temperature. The solid product is recovered by filtration With 2 × 250 mL of 1,2-dichloromethane, 2 × 250 mL of petroleum ether Wash, air dry, then vacuum in 50 ° C oven For overnight. Off-white solid, 4-methyl-4-picoline iodide Nium (106 g) was obtained. 35 g of N-methyl-4-picolinium iodide in 200 mL of water 24.3 g of ammonium hexafluorophosphate (Al Treated with Aldrich Chemical Co. When the two solutions were mixed, a precipitate formed. The precipitate was collected by filtration and 2 × 10 Wash with 0 mL water, suction dry, then dry in a vacuum oven at 40 ° C. overnight. Was. 30 g of white solid N-methyl-4-picolinium hexafluorophos And obtained by differential scanning calorimetry mp. 210 °. Product The determination was confirmed by IR and NMR spectroscopy.   Various modifications and variations of this invention may be made without departing from the scope and spirit of this invention. Further modifications will be apparent to those skilled in the art, and the present invention is not limited to the exemplary embodiments described herein. It should be understood that the embodiments should not be inadvertently limited.

───────────────────────────────────────────────────── フロントページの続き (51)Int.Cl.7 識別記号 FI テーマコート゛(参考) C09J 163/00 C09J 163/00 (81)指定国 EP(AT,BE,CH,DE, DK,ES,FI,FR,GB,GR,IE,IT,L U,MC,NL,PT,SE),OA(BF,BJ,CF ,CG,CI,CM,GA,GN,ML,MR,NE, SN,TD,TG),AP(GH,KE,LS,MW,S D,SZ,UG,ZW),EA(AM,AZ,BY,KG ,KZ,MD,RU,TJ,TM),AL,AM,AT ,AU,AZ,BA,BB,BG,BR,BY,CA, CH,CN,CU,CZ,DE,DK,EE,ES,F I,GB,GE,GH,HU,IL,IS,JP,KE ,KG,KP,KR,KZ,LC,LK,LR,LS, LT,LU,LV,MD,MG,MK,MN,MW,M X,NO,NZ,PL,PT,RO,RU,SD,SE ,SG,SI,SK,SL,TJ,TM,TR,TT, UA,UG,UZ,VN,YU,ZW (72)発明者 パーカー,ダグラス エス. アメリカ合衆国,ミネソタ 55133―3427, セント ポール,ポスト オフィス ボッ クス 33427 (72)発明者 パラゾット,マイケル シー. アメリカ合衆国,ミネソタ 55133―3427, セント ポール,ポスト オフィス ボッ クス 33427──────────────────────────────────────────────────続 き Continued on the front page (51) Int.Cl. 7 Identification symbol FI Theme coat ゛ (Reference) C09J 163/00 C09J 163/00 (81) Designated country EP (AT, BE, CH, DE, DK, ES, FI, FR, GB, GR, IE, IT, LU, MC, NL, PT, SE), OA (BF, BJ, CF, CG, CI, CM, GA, GN, ML, MR, NE, SN, TD, TG), AP (GH, KE, LS, MW, SD, SZ, UG, ZW), EA (AM, AZ, BY, KG, KZ, MD, RU, TJ, TM), AL, AM, AT, AU, AZ, BA, BB, BG, BR, BY, CA, CH, CN, CU, CZ, DE, DK, EE, ES, FI, GB, GE, GH, HU, L, IS, JP, KE, KG, KP, KR, KZ, LC, LK, LR, LS, LT, LU, LV, MD, MG, MK, MN, MW, MX, NO, NZ, PL, PT , RO, RU, SD, SE, SG, SI, SK, SL, TJ, TM, TR, TT, UA, UG, UZ, VN, YU, ZW (72) Inventor Parker, Douglas S. Minnesota 55133 ―3427, St. Paul, Post Office Box 33427 (72) Inventor Parazod, Michael Sea. Minnesota, United States 55133―3427, St. Paul, Post Office Box 33427.

Claims (1)

【特許請求の範囲】 1.硬化可能な組成物であって: a)0重量パーセントより多量であり、75重量パーセントまでのエポキシ樹 脂と、 b)該硬化可能なエポキシ樹脂のための有効量の硬化剤と、必要に応じて該硬 化剤のための増感剤および促進剤の一方または両方と、 c)総エポキシ−フルオロポリマー組成物の重量に対して25から100重量 パーセント未満の十分に予備重合された未架橋フルオロポリマーと、 d)必要に応じて、ポリオレフィンおよびポリアミドの一方または両方を 含む硬化可能な組成物。 2.前記フルオロポリマーがポリ(テトラフルオロエチレン)、ポリ(テトラフ ルオロエチレン−コ−ヘキサフルオロプロピレン)、ポリ(エチレン−コ−テトラ フルオロエチレン)、ポリ(エチレン−コ−テトラフルオロエチレン−コ−ヘキサ フルオロプロピレン)、ポリ(フッ化ビニリデン)、ポリ(クロロトリフルオロエチ レン)、およびテトラフルオロエチレンとヘキサフルオロプロピレンとフッ化ビ ニリデンとのターポリマー(THV)からなる群から選択される請求項1記載の 組成物。 3.前記フルオロポリマーが0.01〜20モルパーセントの範囲の脱フッ化 水素化フルオロポリマーを含有する請求項1または2記載の組成物。 4.前記エポキシ樹脂が1,2−、1,3−および1,4−環状エーテルを1 つ以上含有する請求項1乃至3のいずれかに記載の組成物。 5.前記硬化剤が光硬化剤および170℃以上の温度において活性化される熱 硬化剤からなる群から選択される請求項1乃至4のいずれかに記載の組成物。 6.前記光硬化剤がヨードニウム錯塩およびスルホニウム錯塩並びに有機金属 錯塩からなる群から選択され、前記熱硬化剤が脂肪族および芳香族第1級および 第2級アミン、脂肪族および芳香族第3級アミン、第4級アンモニウム塩、フル オレンジアミン、3フッ化ホウ素錯体、ヒドラジン、グアニジン並びにピリジニ ウムイオン、キノリニウムイオン、ベンゾオキサゾリウムイオン、ベンゾチアゾ リウムイオン、ヨードレニウムイオン、アンモニウムイオンおよびホスホニウム イオンの塩からなる群から選択される請求項5記載の組成物。 7.前記エポキシ樹脂が、芳香族ポリエポキシド、脂肪族環状ポリエポキシド および脂肪族ポリエポキシドからなる群から選択される請求項1乃至6のいずれ かに記載の組成物。 8.ホットメルト接着剤、基材上の被覆、接着テープ構成物に組み込まれたも のの1つ以上である請求項1乃至7のいずれかに記載の組成物。 9.請求項1乃至8のいずれかに記載の硬化した組成物。 10.フルオロポリマー−エポキシ半−IPNを含有する請求項9記載の硬化 した組成物。 11.基材上の被覆、構造接着剤、多層集成物に組み込まれたものおよび自己 支持フィルムまたはフォームの1つ以上である請求項1乃至10のいずれかに記 載の硬化した組成物。 12.方法IまたはIIのステップを含む、請求項10記載の半−相互貫入ポ リマーを製造するための方法: 方法 I: a)触媒の熱活性化温度より低い温度において、 1)硬化可能なエポキシ樹脂と、 2)該硬化可能なエポキシ樹脂のための、活性化可能温度が170℃以上 である有効量の熱硬化剤と、 3)十分に予備重合され、未架橋であり、必要に応じて20重量パーセン トまでが脱フッ化水素化されたフルオロポリマーと、 4)必要に応じて、ポリオレフィンおよびポリアミドの少なくとも一方 を含む混合物を提供するステップと、 b)前記エポキシ樹脂の硬化を行うのに十分な時間、温度を該触媒の熱活性化 温度より高く上昇させるステップを含む方法;および 方法 II: a)1)硬化可能なエポキシ樹脂と、 2)該硬化可能なエポキシ樹脂のための有効量の光開始剤と、 3)十分に予備重合された未架橋のフルオロポリマーと、 4)必要に応じて、ポリオレフィンおよびポリアミドの少なくとも一方 を含む混合物を提供するステップと、 b)前記エポキシ樹脂の硬化を行うのに十分な時間、前記混合物をUV放射線 に暴露するステップと を含む方法。[Claims] 1. A curable composition comprising: a) greater than 0 weight percent, up to 75 weight percent of an epoxy resin; b) an effective amount of a curing agent for the curable epoxy resin; One or both of a sensitizer and an accelerator for the curing agent; and c) from 25 to less than 100 weight percent of a fully prepolymerized uncrosslinked fluoropolymer based on the weight of the total epoxy-fluoropolymer composition. D) a curable composition optionally comprising one or both of a polyolefin and a polyamide. 2. The fluoropolymer is poly (tetrafluoroethylene), poly (tetrafluoroethylene-co-hexafluoropropylene), poly (ethylene-co-tetrafluoroethylene), poly (ethylene-co-tetrafluoroethylene-co-hexafluoropropylene) 2. The composition of claim 1, wherein the composition is selected from the group consisting of:), poly (vinylidene fluoride), poly (chlorotrifluoroethylene), and a terpolymer (THV) of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride. . 3. 3. The composition of claim 1 wherein the fluoropolymer contains a dehydrofluorinated fluoropolymer in the range of 0.01 to 20 mole percent. 4. 4. The composition according to claim 1, wherein the epoxy resin contains one or more 1,2-, 1,3- and 1,4-cyclic ethers. 5. The composition according to any of claims 1 to 4, wherein the curing agent is selected from the group consisting of a photocuring agent and a thermal curing agent activated at a temperature of 170 ° C or higher. 6. The photocuring agent is selected from the group consisting of iodonium and sulfonium complex salts and organometallic complex salts, wherein the thermosetting agent is an aliphatic and aromatic primary and secondary amine, an aliphatic and aromatic tertiary amine, Consists of quaternary ammonium salts, fluorenediamines, boron trifluoride complexes, hydrazine, guanidine and salts of pyridinium ion, quinolinium ion, benzoxazolium ion, benzothiazolium ion, iodorenium ion, ammonium ion and phosphonium ion The composition according to claim 5, which is selected from the group. 7. The composition according to any one of claims 1 to 6, wherein the epoxy resin is selected from the group consisting of an aromatic polyepoxide, an aliphatic cyclic polyepoxide, and an aliphatic polyepoxide. 8. 8. The composition according to any of the preceding claims, wherein the composition is one or more of a hot melt adhesive, a coating on a substrate, and an adhesive tape composition. 9. A cured composition according to any of the preceding claims. 10. 10. The cured composition of claim 9, comprising a fluoropolymer-epoxy semi-IPN. 11. A cured composition according to any of the preceding claims, which is one or more of a coating on a substrate, a structural adhesive, incorporated into a multilayer assembly and a self-supporting film or foam. 12. 11. A method for producing a semi-interpenetrating polymer according to claim 10, comprising the steps of Method I or II: Method I : a) at a temperature below the thermal activation temperature of the catalyst: 1) a curable epoxy resin; 2) an effective amount of a thermosetting agent having an activatable temperature of 170 ° C. or higher for the curable epoxy resin; 3) fully prepolymerized, uncrosslinked and optionally 20 wt. Providing a mixture comprising up to a percentage of a dehydrofluorinated fluoropolymer; 4) optionally comprising a polyolefin and / or a polyamide; and b) a time sufficient to effect curing of the epoxy resin. the method of temperature comprises the step of raising higher than the thermal activation temperature of the catalyst; and methods II: a) 1) and curable epoxy resin, 2) curing possible et Providing an effective amount of a photoinitiator for the xy resin; 3) a fully prepolymerized, uncrosslinked fluoropolymer; 4) optionally, a mixture comprising at least one of a polyolefin and a polyamide; b) exposing the mixture to UV radiation for a time sufficient to effect curing of the epoxy resin.
JP10511654A 1996-08-26 1997-08-01 Fluoropolymer-epoxy resin semi-interpenetrating network composition Pending JP2000516983A (en)

Applications Claiming Priority (5)

Application Number Priority Date Filing Date Title
US2456696P 1996-08-26 1996-08-26
US60/024,566 1996-08-26
US78247697A 1997-01-10 1997-01-10
US08/782,476 1997-01-10
PCT/US1997/013561 WO1998008906A1 (en) 1996-08-26 1997-08-01 Fluoropolymer-epoxy resin semi-interpenetrating network composition

Publications (2)

Publication Number Publication Date
JP2000516983A true JP2000516983A (en) 2000-12-19
JP2000516983A5 JP2000516983A5 (en) 2005-04-07

Family

ID=26698595

Family Applications (1)

Application Number Title Priority Date Filing Date
JP10511654A Pending JP2000516983A (en) 1996-08-26 1997-08-01 Fluoropolymer-epoxy resin semi-interpenetrating network composition

Country Status (5)

Country Link
EP (1) EP0920482A1 (en)
JP (1) JP2000516983A (en)
KR (1) KR100499992B1 (en)
AU (1) AU3904397A (en)
WO (1) WO1998008906A1 (en)

Cited By (8)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2004511641A (en) * 2000-10-14 2004-04-15 ローベルト ボツシユ ゲゼルシヤフト ミツト ベシユレンクテル ハフツング Silicone-modified one-component seal compound
JP2007224183A (en) * 2006-02-24 2007-09-06 Toyo Ink Mfg Co Ltd Energy-sensitive linear acid curable composition
JP2009511297A (en) * 2005-10-11 2009-03-19 シーアールシー フォー アドバンスト コンポジット ストラクチャーズ リミテッド Bonding method of dry reinforcing fiber
JP2009522414A (en) * 2005-12-30 2009-06-11 イー・アイ・デュポン・ドウ・ヌムール・アンド・カンパニー Fluoropolymer coated films useful for photovoltaic modules
JP2011517724A (en) * 2008-04-14 2011-06-16 ダウ グローバル テクノロジーズ エル エルエルシー Use of fillers that undergo an endothermic phase transition to reduce the reaction exotherm of epoxy-based compositions
JP2017171714A (en) * 2016-03-22 2017-09-28 富士電機株式会社 Resin composition
JPWO2025197246A1 (en) * 2024-03-19 2025-09-25
JP7906207B2 (en) 2024-03-19 2026-08-18 ユニマテック株式会社 Adhesive compositions, coverlays, bonding sheets, and electronic substrates

Families Citing this family (20)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
US6518362B1 (en) 1998-02-18 2003-02-11 3M Innovative Properties Company Melt blending polyphenylene ether, polystyrene and curable epoxy
US6235850B1 (en) 1998-12-11 2001-05-22 3M Immovative Properties Company Epoxy/acrylic terpolymer self-fixturing adhesive
US6294270B1 (en) 1998-12-23 2001-09-25 3M Innovative Properties Company Electronic circuit device comprising an epoxy-modified aromatic vinyl-conjugated diene block copolymer
JP3987243B2 (en) * 1999-09-10 2007-10-03 スリーエム イノベイティブ プロパティズ カンパニー Adhesive sheet and adhesive sheet for coating
US6359166B1 (en) 1999-10-08 2002-03-19 3M Innovative Properties Company Oxalate ester blocked phenols
US6387508B1 (en) 2000-09-14 2002-05-14 3M Innovative Properties Company Metal bonding film compositions
DE10148909A1 (en) * 2001-09-26 2003-04-30 Inst Polymerforschung Dresden Components, semi-finished products and profiles, made wholly or partly of plastic
DE102006015499B4 (en) * 2006-03-31 2009-08-27 Radpro International Gmbh thermoluminescence
DE102006057142A1 (en) 2006-12-01 2008-06-05 Henkel Kgaa Metal compounds as initiators
RU2462493C1 (en) * 2011-04-05 2012-09-27 Российская Федерация, от имени которой выступает Министерство промышленности и торговли Российской Федерации (Минпромторг России) Barrier coating composition
KR101857297B1 (en) 2011-12-27 2018-05-14 주식회사 케이씨씨 Resin for electrodeposition coating having trifluoride, method for preparing the same and electrodeposition coating composition comprising the same
WO2013191903A1 (en) 2012-06-18 2013-12-27 3M Innovative Properties Company Powder composition for air polishing the surface of hard dental tissue
EP2742897A1 (en) 2012-12-17 2014-06-18 3M Innovative Properties Company Nozzle head, hand piece and powder jet device for applying a dental material
EP2931171B1 (en) 2012-12-17 2018-08-15 3M Innovative Properties Company Device for dispensing a dental material with locking mechanism
EP2742898A1 (en) 2012-12-17 2014-06-18 3M Innovative Properties Company Powder jet device for dispensing a dental material
US9169393B2 (en) 2013-07-25 2015-10-27 3M Innovative Properties Company Anticorrosion coatings
GB201421373D0 (en) 2014-12-02 2015-01-14 Cytec Ind Inc Modified amine curing agents, their preparation and use in curable compositions
TWI627192B (en) * 2015-03-13 2018-06-21 Murata Manufacturing Co., Ltd. Atomic layer deposition inhibiting material
TWI820229B (en) * 2018-10-17 2023-11-01 日商東洋紡股份有限公司 Thermal conductive resin composition
CN113549169B (en) * 2021-06-15 2022-12-06 南京工业大学 Phenylfluorenamine polymer hole transport material and preparation method and application thereof

Family Cites Families (9)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
GB1031406A (en) * 1963-11-05 1966-06-02 Acheson Ind Inc Low friction materials
US4169187A (en) * 1977-04-01 1979-09-25 E. I. Du Pont De Nemours And Company Powder coating composition of a mixture of epoxy resins
EP0084771A3 (en) * 1982-01-22 1984-02-22 Allied Corporation Method of making a powdered primer coating composition
DE3602800A1 (en) * 1985-06-07 1986-12-11 agru Alois Gruber + Sohn oHG, Bad Hall METHOD FOR THE SURFACE MODIFICATION OF MOLDED BODIES MADE OF POLYVINYLIDEN FLUORIDE
JPS6241218A (en) * 1985-08-19 1987-02-23 Mitsubishi Electric Corp Epoxy resin composition for sealing semiconductor
BR8802120A (en) * 1987-05-18 1988-12-06 Standard Oil Co Ohio ENCAPSULAR PROCESS ARTICLE
JP2803055B2 (en) * 1989-12-04 1998-09-24 東芝ケミカル株式会社 Heat resistant resin composition for molding
JPH0462557A (en) * 1990-07-02 1992-02-27 Canon Inc Photosensitive composition
JPH05186757A (en) * 1992-01-10 1993-07-27 Sumitomo Metal Ind Ltd Adhesive composition for laminated metal plate

Cited By (11)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2004511641A (en) * 2000-10-14 2004-04-15 ローベルト ボツシユ ゲゼルシヤフト ミツト ベシユレンクテル ハフツング Silicone-modified one-component seal compound
JP2009511297A (en) * 2005-10-11 2009-03-19 シーアールシー フォー アドバンスト コンポジット ストラクチャーズ リミテッド Bonding method of dry reinforcing fiber
JP2009522414A (en) * 2005-12-30 2009-06-11 イー・アイ・デュポン・ドウ・ヌムール・アンド・カンパニー Fluoropolymer coated films useful for photovoltaic modules
JP2007224183A (en) * 2006-02-24 2007-09-06 Toyo Ink Mfg Co Ltd Energy-sensitive linear acid curable composition
JP2011517724A (en) * 2008-04-14 2011-06-16 ダウ グローバル テクノロジーズ エル エルエルシー Use of fillers that undergo an endothermic phase transition to reduce the reaction exotherm of epoxy-based compositions
JP2017171714A (en) * 2016-03-22 2017-09-28 富士電機株式会社 Resin composition
US10597526B2 (en) 2016-03-22 2020-03-24 Fuji Electric Co., Ltd. Resin composition
JP7221579B2 (en) 2016-03-22 2023-02-14 富士電機株式会社 resin composition
JPWO2025197246A1 (en) * 2024-03-19 2025-09-25
WO2025197246A1 (en) * 2024-03-19 2025-09-25 ユニマテック株式会社 Adhesive composition, coverlay, bonding sheet, and electronic substrate
JP7906207B2 (en) 2024-03-19 2026-08-18 ユニマテック株式会社 Adhesive compositions, coverlays, bonding sheets, and electronic substrates

Also Published As

Publication number Publication date
KR20000035830A (en) 2000-06-26
KR100499992B1 (en) 2005-07-12
AU3904397A (en) 1998-03-19
EP0920482A1 (en) 1999-06-09
WO1998008906A1 (en) 1998-03-05

Similar Documents

Publication Publication Date Title
KR100499992B1 (en) Fluoropolymer-epoxy resin semi-interpenetrating network composition
DE69823882T2 (en) HYBRID MATERIALS OF PPE / POLYSTYRENE / HARDENABLE EPOXY COMPOSITIONS
US5709948A (en) Semi-interpenetrating polymer networks of epoxy and polyolefin resins, methods therefor, and uses thereof
DE69411740T2 (en) Electrically conductive adhesive compositions
DE2952440C2 (en) Crosslinkable resin composition and its use for making a laminate
KR100397007B1 (en) Semi-interpenetrating polymer network made of epoxy resin and polyolefin resin, preparation method and method of use thereof
US2920990A (en) Structural adhesive compositions
CN1337975A (en) Electronic circuit device comprising an epoxy-modified aromatic vinyl-conjugated diene block copolymer
USRE25625E (en) Structural adhesive compositions
JPH0360328B2 (en)
JP2001098165A (en) Curable resin composition
JP2001105546A (en) Laminate
JPS621649B2 (en)
JP3097259B2 (en) Epoxy resin composition and prepreg
JP3390865B2 (en) Powder coatings for cast iron pipes
JP2006335791A (en) Epoxy resin composition and prepreg containing the same
JPS59207917A (en) Reactive plastisol dispersion composition, manufacture and use
JP3282097B2 (en) Powder coatings for cast iron pipes
WO2021181316A1 (en) Resin composition for electrolyte membrane adhesion, resin film for electrolyte membrane adhesion, and method for producing resin film for electrolyte membrane adhesion
US3419462A (en) Benzoin-type copolymers and glass fabric laminates thereof
JPH01100802A (en) Ultraviolet setting type insulation cable
JP4516343B2 (en) Polyester adhesive composition
JPH04178454A (en) Ultraviolet-curing resin composition
JPH0467721B2 (en)
JP2003105049A (en) Method for manufacturing polyphenol resin

Legal Events

Date Code Title Description
A521 Request for written amendment filed

Free format text: JAPANESE INTERMEDIATE CODE: A523

Effective date: 20040802

A621 Written request for application examination

Free format text: JAPANESE INTERMEDIATE CODE: A621

Effective date: 20040802

A131 Notification of reasons for refusal

Free format text: JAPANESE INTERMEDIATE CODE: A131

Effective date: 20051129

A977 Report on retrieval

Free format text: JAPANESE INTERMEDIATE CODE: A971007

Effective date: 20051110

A601 Written request for extension of time

Free format text: JAPANESE INTERMEDIATE CODE: A601

Effective date: 20060227

A602 Written permission of extension of time

Free format text: JAPANESE INTERMEDIATE CODE: A602

Effective date: 20060424

A521 Request for written amendment filed

Free format text: JAPANESE INTERMEDIATE CODE: A523

Effective date: 20060529

A02 Decision of refusal

Free format text: JAPANESE INTERMEDIATE CODE: A02

Effective date: 20060905

A72 Notification of change in name of applicant

Free format text: JAPANESE INTERMEDIATE CODE: A721

Effective date: 20061204